Hydrological dynamics regulate reactive oxygen species production in the largest freshwater lake of China - Wenkang Li; Siwen Li; Dinggui Wu; Chaoran Guo; Huacheng Xu; Na Song (Water Research, 2026)

A Multi-Index decision framework of optimal gasket selection for tunnel segmental joints: Integrating variable weight and extension cloud model - Huai-Na Wu; Hua-Yong Li; De-Sai Guo; Yu Li; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Unraveling the mechanism of gluten protein restructuring in modulating the cracking behavior of dumpling wrappers during freeze-thaw cycles - Li-Qin Tang; Xiaohong Sun; Xiao-Na Guo; Ke-Xue Zhu (Food Hydrocolloids, 2026)

Targeted regulation and extraction mechanism of rare earth elements and thorium during the decomposition of rare earth concentrates - Xiaowei Zhang; Likai Zang; Feng Guo; Yanhong Hu; Jinxiu Wu; Wenjun Fan; Jianguo Cui; Na Li; Xiaodong Wang; Ruifeng Ma (Minerals Engineering, 2026)

Oxidation mechanism of rice bran protein components induced by microwave plasma: A perspective based on amino acid side chain modification - Chang Liu; Lin Li; Ruichi Guo; Xiangyu Du; Liqi Wang; Na Zhang; Dianyu Yu (Food Hydrocolloids, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Fe(II)-driven abiotic-biotic relay alleviates denitrification bottleneck via chemical nitrite reduction and intracellular carbon - Na Hu; Qi Feng; Chenxi Li; Yuanyuan Liu; Baoli Zhu; Tianci Guo; Lei Tong; Jianbo Shi; Robert A. Sanford; Shuyi Li; Yu He; Yidan Hu; et al. (Water Research, 2026)

Linking hydrogen production pathways with sustainable heavy-duty freight transport: A life cycle environmental and economic assessment in China - Qun Wang; Xuege Li; Mianqiang Xue; Jingwen Wang; Yongzhi Liu; Na Guo; Xueqin Li; Zhiwei Wang (Sustainable Production and Consumption, 2026)

Molecular simulation of 2,3,7,8-TCDD adsorption in nanoporous carbon: Pore structure and competitive effects of H2O and SO2 - Yu-bo Yin; Yu-wen Zhu; Shi Tang; Jie Huang; Guo-qing Chen; Na Li; Zhen Yang; Han-qiao Liu (Journal of Environmental Chemical Engineering, 2026)

Biological recovery of waste lithium-ion battery cathode materials: Recent advancements - Haolin Li; Senshen Yu; Shuaizhe Li; Mengke Dong; Yunke Wang; Huijun Fan; Yadong Wang; Xingyong Li; Na Liu; Xuexiang Fu; Di Cai; Yanliang Guo; et al. (Journal of Environmental Chemical Engineering, 2026)

Enhancing bread storage stability with chitosan oligosaccharides of different molecular weights: inhibiting spoilage microorganisms and retarding starch retrogradation - Li-Hong Du; Xiao-Na Guo; Xiao-Hong Sun; Ke-Xue Zhu (Carbohydrate Polymers, 2026)

Spatiotemporal characteristics of O3 pollution and source apportionment of reactive precursors in Shenyang, China - Na Jiang; Sixiao Guo; Wenyu Fan; Xiaochao Li; Changfeng Liu (Atmospheric Pollution Research, 2026)

GLSP ameliorates monocrotaline-induced pulmonary arterial hypertension through inhibition of the PI3K/AKT and MAPK signaling pathways - Yingying Wei; Siying Zuo; Na Deng; Haijun Guo; Liwei You; Yaping Zuo; Yan Wu; Zhangrong Chen; Wei Li; Xiaoyun Si (Journal of Molecular Histology, 2026)

Enzymatic Preparation of Ejiao (Colla Corii Asini) Peptides and Their Preliminary Mechanism of Melanogenesis Inhibition - Xichao Fu; Shangwei Guo; Meijin Li; Zhijie Chen; Dan Liu; Cuicui Men; Na Yang; Xiaobo Duan; Xiaolu Tang; Yaru Zhang; Haibin Liu; Minghao Liu; et al. (International Journal of Peptide Research and Therapeutics, 2026)

Phenylbutene dimers and saturated phenylbutene derivatives from Zingiber montanum with anti-inflammatory potential - Zhi-hang Wu; Lu Chen; Jin-na Zhao; Lv-you Wan; Fa-xiang Guo; Lei Zhang; Li-bo Wang; Jin-hui Wang; Xian-mei Piao (Phytochemistry, 2026)

The transcription factor SbWRKY6 confers cadmium tolerance via activating SbPLAC8–17 expression in sorghum - Shan Cao; Jiqing Zhang; Zhengyu Guo; He Wang; Zengting Chen; Simin Li; Na Sui (Journal of Hazardous Materials, 2026)

Mg/Ca ratio-regulated phase differentiation of microbially derived CaCO3 and its effects on Cu2+, Cd2+, and Pb2+ immobilization - Kaiming Hu; Yanyang Zhao; Yishui Han; Zuozhen Han; Ruirui Meng; Xiao Gao; Jie Li; Na Guo (Journal of Hazardous Materials, 2026)

Pickering emulsion stabilized by immobilized lipase for OPO synthesis and acyl migration inhibition - Ruichi Guo; Xiangyu Du; Lin Li; Liqi Wang; Na Zhang; Tong Wang; Dianyu Yu (Food Research International, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Polystyrene microplastic exposure induces hepatic damage via immune-modulated autophagy and ferroptosis in Nile tilapia (Oreochromis niloticus) - Feilong Wang; Xiaolong Fan; Xiaomeng Guo; Na Guo; Tian Gao; Changle Zhao; Yuanyuan Li; Haiyan Xu; Fan Bai; Yixin Chen; Deshou Wang; Lina Sun; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Effects of short-term continuous cropping on soil environmental factors and microbial communities of Pinellia ternata (Thunb.) Breit. - Guoli Wang; Yijia Zhao; Na Liu; Yu Tong; Wen Yin; Pan Li; Chunyu He; Yao Guo (Plant and Soil, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Nonlinear dynamics and optimal deployment of a deep-ocean mining riser with surface-mounted flow-disturbing robots - Shanfei Fan; Xiaoqiang Guo; Kelun Yang; Reza N. Jazar; Edson Denis Leonel; Nerguibaatar Tsend; Xianbin Liu; Yuwen Wang; Liming Dai; Jun Liu; Ning Zong; He Chen; et al. (Ocean Engineering, 2026)

MIL-101(Cr) disrupts algal carbon fixation by intercepting photosynthetic electron flow: Implications for aquatic primary productivity - Kun Lu; Zian Wang; Yuxin Wang; Shuyang Chen; Na Li; Fangjie Guo; Lei Xu; Meizhen Wang (Journal of Hazardous Materials, 2026)

A comparative bioprocess for nutrient reclamation: Suspended versus immobilized Virgibacillus salexigens XYD drives struvite recovery from eutrophic saline water - Na Guo; Yueming Zhao; Shuqi Wang; Yanhong Zhao; Yudong Xu; Memon Kashif Ali; Huaxiao Yan; Hui Zhao; Zuozhen Han; Maurice E. Tucker; Chao Han; Yanyang Zhao; et al. (Journal of Environmental Management, 2026)

Associations between prenatal exposure to indoor air pollution and ambient particulate matter with infant growth - Jinlang Lyu; Tiantian Li; Shuang Zhou; Xin Yuan; Zheng Bao; Na Han; Gongbo Chen; Yuelong Ji; Qin Li; Jue Liu; Hui Wang; Jianlin Hu; et al. (Journal of Environmental Sciences, 2026)

Conductive nanofiber veils: Their preparation and application to effectively increase through-thickness electrical conductivity and interlaminar toughness of epoxy CFRPs - Yan Li; Gang Zhou; Na Ning; Lei Chen; Zhengyan Guo; Yi Wei (Chemical Engineering Journal, 2026)

Chemical composition of the endogenous fungus Fusarium sp. L-3 derived from Chinese Qinan agarwood - Ming-Li Han; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Na Xiao; You-Xing Zhao (Natural Product Research, 2026)

Detection and Defense Against False Data Injection Attacks for Secure Energy Management in Hybrid Electric Ships - Hao Sun; Na Li; Mo Guo; Jingwei Wei; Tianqing Yuan (Journal of Marine Science and Engineering, 2026)
Reliable battery state awareness is essential for energy management and power allocation in hybrid electric ships. However, battery management systems are increasingly exposed to False Data Injection Attacks (FDIAs) in intelligent connected environments, which can distort State of Charge (SOC) estimation and compromise the operational reliability of shipboard power systems. To address this challenge, this paper proposes a closed-loop “Modeling-Detection-Defense” framework for secure SOC estimation in marine cyber-physical energy systems. First, a stealthy FDIA model is developed based on battery dynamics and physical consistency constraints. Second, a hybrid detection method combining unsupervised and supervised learning is proposed to identify attacks. Finally, a long short-term memory network is employed to reconstruct compromised measurements and provide reliable SOC information for continuous energy management. Experimental results demonstrate that the proposed framework mitigates SOC estimation deviations caused by FDIAs. In addition, it effectively reduces power allocation errors and energy losses, thereby improving the cyber-resilience, operational reliability, and energy efficiency of hybrid ship power systems.

Establishment and identification of an embryonic cell line of Chinese sturgeon (Acipenser sinensis) and its application in germplasm conservation and disease resistance - Qi Zhang; Juanjuan Liu; Zhihong Gong; Wenjie Li; Chenfei Guo; Jiaqi Mai; Yuqi Sun; Songlin Chen; Na Wang (Aquaculture, 2026)

Towards ultra-low sulfur dioxide emissions in copper industry: An integrated analysis based on full-process material-energy-pollution flows - Na Li; Chengkang Gao; Zhenjiang Guo; Menghui Zhang (Process Safety and Environmental Protection, 2026)

Insight into torrefaction treated biomass on physicochemical properties and pyrolysis products using grey relational analysis - Jingjing Li; Zhiwei Wang; Na Guo; Nan Xu; Shuaihua Guo; Hongxun Zhang; Tingzhou Lei (Process Safety and Environmental Protection, 2026)

The balance of complexation and decomposition determines the sequestration behaviors of heavy metals from acidic wastewater by chelating captures - Na Ma; Xuejun Guo; Bojun Li; Siwen Leng (Journal of Cleaner Production, 2026)

Research on the interface adsorption and emulsion properties of microwave cold plasma oxidized modified rice bran protein-phloridzin binary complex - Chang Liu; Ruichi Guo; Lin Li; Liqi Wang; Na Zhang; Weining Wang; Dianyu Yu (Food Research International, 2026)

Unravelling flavor formation in Chinese steamed bread made with fermented glutinous rice wine dough: insights from microbial succession, metabolomics, and volatile profiling - Jia-Xuan Li; Feng-Ping Qin; Meng-Ting Chen; Yu-Yu Liu; Xiao-Na Guo; Ke-Xue Zhu; Fei Gao; Jun-Jie Xing (Food Research International, 2026)

Microglial Alkbh5 Deficiency Alleviates Chronic Restraint Stress-Induced Depression-like Behaviors in Mice - Ao Li; Lu Han; Jia Guo; Na Zhang; Ranxu Liu; Jingdan Zhang; Xiaoheng Li; Zengqiang Yuan; Jinbo Cheng (Neuroscience Bulletin, 2026)

A Humanized Knock-in Mouse Model of the PSEN1 V97L Mutation from a Major Chinese Alzheimer’s Disease Pedigree Reveals Early Neuroinflammation - Lu Dai; Sirong Lv; Huimin Guo; Zizhao Li; Jiaying Li; Yujia Wang; Miaomiao Du; Donghui Wu; Kunhe Ma; Na Wu; Jing Zhang; Baian Chen (Neuroscience Bulletin, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Time-Series Transcriptomics of a Gill Cell Line (BTG) from Chinese Bahaba (Bahaba taipingensis) During ISKNV Infection (3–24 hpi) - Chenfei Guo; Zhihong Gong; Fei Fang; Xihong Li; Lei Wang; Na Wang; Zhangfan Chen; Lin Yan; Kuoqiu Yan; Guobin Hu; Songlin Chen (Fishes, 2026)
The Chinese bahaba (Bahaba taipingensis), an endangered marine fish, is highly vulnerable to infectious spleen and kidney necrosis virus (ISKNV). In this work, we developed a gill filament-derived cell line, designated BTG, to investigate how these cells respond to ISKNV over time, specifically from 3 to 24 h post-infection (hpi). BTG cells grew steadily, displayed a diploid chromosome number of 2n = 48, demonstrated high transfection efficiency, and were highly susceptible to viral infection. Characteristic cytopathic effects (CPEs) became noticeable as early as 6 hpi at 27 °C. RNA-seq profiling showed that the number of differentially expressed genes (DEGs) steadily increased with time. Standard enrichment analysis at individual time points (3, 6, 12, and 24 hpi) highlighted pathways mainly involved in DNA replication, cell cycle control, ribosome assembly, transcription and translation, mismatch repair, and cell adhesion. Temporal clustering analysis, however, revealed hidden patterns in immune gene expression. Genes that were consistently downregulated were enriched in immune-related pathways, including ECM–receptor interaction, cytokine–receptor signaling, PI3K–AKT, and Wnt signaling, indicating prolonged suppression of host defense mechanisms. In contrast, clusters of genes transiently upregulated during the first 6 h post-infection were associated with antiviral and innate immune pathways, such as NF-κB, JNK, IRF3, IRF7, caspases, JAK, MHC I, and lysosome-related functions, suggesting a rapid but short-lived antiviral response. Genes that were continuously upregulated were primarily involved in nucleic acid replication and protein synthesis, reflecting a gradual host cell reprogramming to support viral replication. Taken together, these findings reveal a temporal shift in BTG cells from an initial burst of immune activity to immune suppression, accompanied by enhanced viral replication. The BTG cell line thus represents a valuable in vitro model for dissecting ISKNV–host interactions and offers new perspectives on the molecular strategies employed by megalocytiviruses in B. taipingensis.

The EAL domain protein YjcC contributes to the pathogenicity of Pseudomonas plecoglossicida - Li Cao; Yuanyuan Zhou; Na Guo; Chengqi Xiong; Qionglin Liu; Xiaoyue Dang; Ruoyu Liu; Xiang-Yang Zhang; Xinhua Chen (Aquaculture International, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Physicochemical characteristics changes in post-ripening of wheat flour mill streams: Effects on dough properties and steamed bread quality - Meng-Li Zhang; Xiao-Na Guo; Xiao-Hong Sun; Ke-Xue Zhu (Food Hydrocolloids, 2026)

Time-dependent biphasic dysregulation of autophagy and innate immunity underlies polystyrene microplastics-induced hepatotoxicity in Nile tilapia - Feilong Wang; Xiaomeng Guo; Na Guo; Xiaolong Fan; Haiyan Xu; Yuanyuan Li; Tian Gao; Yixin Chen; Changle Zhao; Lina Sun; Deshou Wang; Xin Xie; et al. (Aquatic Toxicology, 2026)

An integrated multi-omics approach for deciphering podophyllotoxin-induced nephrotoxicity via the microbiome-gut-kidney (MGK) axis based on the toxicological evidence (TEC) concept - Xiaole Guo; Yu Wang; Lei Wang; Yan Lei; Ri-na Sa; Lili Li; Shengnan Xia; Xiaoming Lin; Chuanxin Liu; Yuanyang Shao (Journal of Molecular Histology, 2026)

Post-earthquake road accessibility assessment in mountainous counties incorporating geological hazard density correction: A case study of Pingshan County, Hebei Province - Qiu-na Guo; He Zhang; Hong-yu Wang; Fan Yang; Jiang Li; Si-yu Liu (Applied Geophysics, 2026)

Stepwise Gradient in Fundamental Individualised Niche Differentiation Across Soil Microbiomes - Huaiqiang Liu; Juan Xu; Yihui Guo; Zhenyuan Lei; Na Wang; Wenya Wei; Liping Qu; Minchun Li; Yarong Feng; Wei Xie (Molecular Ecology, 2026)
Individual microbes often respond differently to the same environment, yet the magnitude of such niche variation inherent to individuals remains unresolved and is anticipated to differ substantially from community‐level average responses. We conducted metagenomic binning on monthly time‐series soil samples from three sites across seasonal cycles. By considering 440,571 genes as dimensions of the fundamental individualised niche (FIN), we traced FIN trajectories of archaea and bacteria during warming, cooling, and turning periods. We found that neither mean temperature nor temperature difference had a significant effect on FIN breadth or overlap. Instead, we discovered a temporally constant, stepwise gradient of niche differentiation across taxonomic categories. At the interdomain level (Archaea vs. Bacteria), niche overlap is approximately 25%, rising to ~40% at the interphylum level and ~60% at the interorder level. This discontinuous gradient likely marks the limit boundaries of niche variation, is closely linked to functional synergy within FINs, and provides a preliminary comparable ecological carrying capacity for each niche step, particularly regarding the interdomain balance.

Synergistic enhancement of industrial adaptability in Lactiplantibacillus plantarum BF_15 through glutathione-mediated redox and DNA repair pathways - Yalin Liu; Na Zhang; Aixin Guo; Hongjie Liu; Dongyao Li; Chen Li; Hongyan Kang; Hongtao Tian (World Journal of Microbiology and Biotechnology, 2026)

Influence of salinity on the dynamic improving nutritional value of channel catfish (Ictalurus punctatus): Insights from targeted and untargeted metabolomics and antioxidant capacity analysis - Zhen Li; Yali Yu; Quanyou Guo; Na Lin; Xiaorong Lu; Jie Peng; Tao Mao; Yuntao Zhou; Lang Zhang; Liu Fang (Aquaculture, 2026)

Geographic discrimination of Sauce-flavor rounded-base Baijiu using GC–MS/MS combined with multivariate analysis and machine learning - Sen Luo; Yi Shen; Wei Cheng; Na Wang; Yadong Zhang; Jian Wang; Di Chang; Juxiu Li; Xinguang Guo; Hongbo Gao (Food Chemistry, 2026)

In situ arming of NETs for targeted delivery of redox-modulating liposomes to eradicate intracellular bacteria in sepsis - Liya Yang; Na Yin; Tongge Wang; Ruilin Chao; Qiang Yang; Yifei Gao; Shenyao Jin; Yiman Chen; Jian Li; Ling Guo; Min Feng (Chemical Engineering Journal, 2026)

Serum Endogenous Opioid Levels are Associated with Self-Injury Severity in Adolescents with Non-Suicidal Self-Injury and Comorbid Depression - Jin-Jun Ding; Xiao-Li Liu; Ang Li; Yi-Yao Liang; Yu-Bo Wang; Xiao-Na Zhu; Jie Li; Jie Weng; Lan Yan; Wen-Wen Duan; Zi-Chen Zhang; Ti-Fei Yuan; et al. (Neuroscience Bulletin, 2026)

A state-of-the-art review of accurate and rapid prediction methods for thermal striping phenomenon in nuclear reactors - Mohsin Raza; Ikram UI Haq; Waqar ul Hassan; Jun-Liang Guo; Hong-Na Zhang; Xiao-Bin Li; Yue Wang; Wei-Hua Cai; Shu-Qi Meng; Fang Chen; Yu-Long Mao; Feng-Chen Li (Annals of Nuclear Energy, 2026)

Superhydrophilic and underwater superoleophobic chitin nanocrystals/ palygorskite nanoclays membrane for multifunctional oil/water emulsion separation - Chenglong Wang; Chenglan Zhang; Jiajie Li; Chun Song; Chenchen Lu; Chenxin Guo; Chunyu Chang; Bo Duan; Na Peng (Journal of Environmental Chemical Engineering, 2026)

Improvement of the quality of whole grain highland barley slurry through thermal pre-treatment under turbulent conditions: Lubrication, microstructure, and rheological - Bo-Hui Li; Yi-Peng Bai; Xiao-Na Guo; Xiao-Hong Sun; Ke-Xue Zhu (Food Chemistry, 2026)

Photothermal-enhanced adsorption system based on ZIF-67-derived CoS2/MoS2 and MXene-functionalized biomass carbon aerogel for efficient removal of strontium and cesium from aqueous matrices - Na Yang; Xu Guo; Jing Yu; Hongsen Zhang; Rumin Li; Lele Wang; Qi Liu; Jun Wang (Desalination, 2026)

Integrated basin-scale assessment of legacy and emerging PFAS in the Xiangjiang River Basin, China: Occurrence, source apportionment, and risk prioritization - Da-Ying Lin; Li-Xin Hu; You-Sheng Liu; Jin-Na Zhang; Guang-Guo Ying (Water Research, 2026)

Interpretable data-driven modeling of total phosphorus dynamics from 2005 to 2024 in a large shallow lake - Weipeng Lin; Yongqiang Zhou; Ze Ren; Wei Zou; Hongwei Guo; Na Li; Yunlin Zhang; James Elser; R. Iestyn Woolway; Kun Shi; Guangwei Zhu; Boqiang Qin; et al. (Water Research, 2026)

Experimental investigation on adiabatic two-phase frictional pressure drop of R290, R600a, and their mixtures in a horizontal minichannel - Na Liu; Hao Ji; Yeyi Liu; Run Li; Dezheng Sun; Qian Zhao; Jianxiang Guo (International Journal of Refrigeration, 2026)

Analysis and regulation of baijiu aroma-active compounds: integrating metabolomics, sensory genomics, and artificial intelligence - Wei Cheng; Na Li; Tianquan Pan; Qingyun Zhu; Wei Lan; Gengdian Liu; Yuxi Guo; Xuefeng Chen (Food Research International, 2026)

Impacts of gluten aggregation behavior on the gassing properties of steamed bread during the wheat flour post-ripening - Meng-Li Zhang; Xiao-Na Guo; Xiao-Hong Sun; Ke-Xue Zhu (Food Hydrocolloids, 2026)

Biomineralization induced by Shigella dysenteriae JS3: The mechanism, and the differences between biotic and abiotic whewellite and struvite - Na Guo; Jizheng Qiao; Shuhua Zhang; Shengzhe Gao; Yanhong Zhao; Chao Han; Hui Zhao; Yanyang Zhao; Xiao Gao; Ruirui Meng; Bin Cao; Yu Li; et al. (Chemical Geology, 2026)

Life cycle perspective on biochar-catalyzed co-pyrolysis of biomass and plastic waste across multiple treatment scenarios - Qun Wang; Zhuo Li; Zhiwei Wang; Gaofeng Chen; Na Guo; Xuege Li; Tingzhou Lei (Bioresource Technology, 2026)

Crustal structure and tectonic implications of the Southern Central Asian Orogenic Belt: New insights from gravity, magnetic, and magnetotelluric imaging - Chutong Chen; Na Li; Lingxiao Zhang; Hongying An; Chang’an Guo; Xing Fu; Songda Lei; Guicai Yang; Junjie Fan; Weiheng Yuan; Hao Wang; Bin Wang; et al. (Tectonophysics, 2026)

Impacts of iron additives on enzymatic activities and nitrogen cycling during composting: Microbial and biochemical insights - Yang Wang; Hong-Yi Wu; Shuang-Yan Jia; Hao-Duo Bai; Kuok Ho Daniel Tang; Xiu-Na Ren; Zhixin Zhang; Yao Yiqing; Guo Xiaohui; Chugang Mei; Rong-Hua Li (Journal of Cleaner Production, 2026)

Artificial sweeteners and antibiotics enhance the dissemination and diversity of antibiotic resistance genes in a soil-water continuum - Chen-Xi Fu; Qian Xiang; Ran Li; Na-Qi Cui; Bin Guo; Dong Zhu; Min Qiao (Journal of Environmental Chemical Engineering, 2026)

Ferrocene carboxylic acid doped nickel iron hydroxide with strong built-in electric field for oxygen evolution reaction - Xin-Jie Tian; Ruo-Xin Wang; Yi-Lin Dong; Yue-Ming Li; Si-Jia Guo; Na Xu; Guanqun Han; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Black phosphorus quantum dots regulate inflammation and neural stem cells differentiation via Notch1 signaling through cell adhesion - Lu Chen; Yongyuan Guo; Lusen Shi; Shiji Zhang; Linlin Jiang; Yong Chang; Haoran Liu; Zihang Wang; Na Li; Shiqing Feng (Chemical Engineering Journal, 2026)

Pectic polysaccharides from Mongolian medicinal Hypecoum leptocarpum: Structure and ulcerative colitis amelioration via gut microbiota and intestinal inflammation regulation - Cunwuliji Na; Xiang Shi; Jicheng Fu; Jiahao Li; Hongyu Jiang; Zhiwei Guo; Hongyan Lai; Zhipeng Zhang; Longyan Zhao; Qingxia Yuan; Baoshun Zhang (Carbohydrate Polymers, 2026)

Estuarine plumes: Modulators of dissolved organic matter molecular signatures and biogeochemical fate in coastal ecosystems - Guodong Sun; Na Wang; Wenbo Wang; Yihui Guo; Juan Xu; Zijia Zeng; Penghui Du; Penghui Li; Chen He; Quan Shi; Dongxiao Wang; Wei Xie (Marine Pollution Bulletin, 2026)

Swine farming emissions drive deterministic assembly of antibiotic resistance genes in receiving River: A new ecological perspective - Chang Liu; Chaoran Li; Xinyan Guo; Liyuan Wang; Na Wang (Water Research, 2026)

Application of an innovative BMask R-CNN-DAT enhanced with feature extraction and boundary awareness in tunnel leakage detection - Yu Li; Huai-Na Wu; Hong-Zhan Cheng; De-Sai Guo; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Catalytic co-pyrolysis of rice straw and polystyrene for selective production of monocyclic aromatic hydrocarbons - Na Guo; Zhiwei Wang; Ruijie Liu; Huina Zhu; Gaofeng Chen; Xueqin Li; Qun Wang; Hongxun Zhang; Tingzhou Lei (Process Safety and Environmental Protection, 2026)

Comprehensive analysis of metabolic response in Arabidopsis thaliana under heavy metal stress by mass spectrometry - Zhongyan Zhou; Donghao Li; Na Wang; Xiujuan Hong; Wen Su; Cheng Guo; Chongsheng He; Lei Yue (Journal of Hazardous Materials, 2026)

Sustainable ethylene production: A life cycle perspective on oil, coal, and natural gas derived industrial pathways in China - Zhen Yang; Yu-wen Zhu; Na Li; Guo-qing Chen; Yu-bo Yin; Tian-ming Ma; Han-qiao Liu (Journal of Cleaner Production, 2026)

Bet-hedging and division of labor: How phenotypic heterogeneity helps foodborne pathogens adapt to diverse environmental stresses - Lijie Wang; Chenfei Li; Yan Wang; Na Guo (Food Research International, 2026)

Dual-confined Cu nanoclusters/InOx nanolayers on AlOOH support: Engineering interfacial structure for enhanced photothermal catalytic CO2 hydrogenation - Guirong Yu; Na Li; Yuhao Guo; Tingjiang Yan (Chemical Engineering Journal, 2026)

Hepatic cyp24a1 serves as a biomarker for diagnosing polystyrene microplastic exposure in Nile tilapia (Oreochromis niloticus) - Feilong Wang; Haiyan Xu; Xiaomeng Guo; Xiaolong Fan; Yuanyuan Li; Tiao Gao; Xin Xie; Na Guo; Fan Bai; Yixin Chen; Changle Zhao; Deshou Wang; et al. (Aquatic Toxicology, 2026)

Resveratrol Attenuates H2O2-induced Aging and Apoptosis in Mouse Hippocampal Neuron HT22 Cells by Activating Autophagy via the SIRT1/FoxO1 Signaling Pathway - Minghui Cai; Qi Guo; Jiaxin Li; Xiaoqi Dai; Huiyu Su; Wenwen Zhang; Na Qiang; Geng Li; Zihan Jin; Hui Zhu (Molecular Neurobiology, 2026)

Cellulose acetoacetate carbanion ion pair organocatalyst in homogenous catalysis of CO2 fixation and heterogenous recycle - Yanqi Shi; Jiahui Ma; Zhenjiang Li; Xin Yuan; Xin Zou; Na Shi; Ziqi Liu; Min Zhang; Hui Zhao; Kai Guo (Sustainable Chemistry and Pharmacy, 2025)

Multiomic insights into the regulatory mechanism of anammox consortia: Interspecies cooperation, degradation and self-adaptation to plasticizer stress - Ge-Ge Wu; Jing-Ao Jin; Na-Na Han; Wen-Li Guo; Nian-Si Fan; Ren-Cun Jin (Journal of Hazardous Materials, 2025)

Evaluating the impact of battery electric vehicle and hydrogen fuel cell vehicle deployment on emissions in China's light-duty passenger vehicle fleet: A scenario-based well-to-wheel analysis - Qun Wang; Xuege Li; Mianqiang Xue; Zhiwei Wang; Yongzhi Liu; Gaofeng Chen; Xinxin Wang; Na Guo (Journal of Cleaner Production, 2025)

Impacts of gluten protein characteristics on the cracking behavior of dumpling wrappers during freeze-thaw cycles - Li-qin Tang; Xiaohong Sun; Xiao-Na Guo; Ke-Xue Zhu (Food Chemistry, 2025)

Targeted-nanoformulation of cannabidiol attenuates endothelial injury and platelet hyperactivation for combating silicosis - Sirong Chang; Yue Sun; Wenyue Zhang; Yi Guo; Huning Zhang; Nan Li; Ran An; Mengsi Xiao; Siwei Zou; Na Zhang; Kai Wang; Anning Yang; et al. (Chemical Engineering Journal, 2025)

Engineering V-based Prussian blue analogue cathodes toward ultrahigh capacity and rate capability in aqueous zinc-ion batteries - Yan Chen; Na Shen; Xinyu Guo; Chang Li; Chengcheng Zhu; Nan Jiang; Xi Liu; Wenjun Deng; Rui Li (Chemical Engineering Journal, 2025)

A new norlignan and other compounds from Artemisia frigida Willd - Xin-Ya Dong; Ru-Ya Li; Hong-Xia Tang; Ya-Jie Li; Jun Chen; Jin-Guo Luo; Na Yu; Xiang-Wei Xu; Xu-Dong Zhou (Biochemical Systematics and Ecology, 2025)

Comparative Evaluation of Spores and Vegetative Forms of Bacillus subtilis and Bacillus licheniformis on Probiotic Functionality In Vitro and In Vivo - Hua Xie; Tianfei Yu; Qiwen Zhou; Kai Na; Shuang Lu; Li Zhang; Xiaohua Guo (Probiotics and Antimicrobial Proteins, 2025)

Synergistic electromagnetic and chemical enhancements in Al/C3N4/Ag@C for Raman-based chlortetracycline sensing - Jingyi Sun; Lujie Li; Tingting Zhang; Na Jiang; Zishan Guo; Congying Li; Weihua Li; Xianhuai Huang; Yan Li; Rui Lu (Analytica Chimica Acta, 2025)

Glioma angiogenesis phosphoproteome landscape and biomarker sets identified with phenome-centered multiomics toward 3P medical approaches - Xiaoxia Gong; Tianyao Guo; Chunlin Li; Zhijun Li; Xuejun Li; Lamei Yang; Na Li; Xianquan Zhan (EPMA Journal, 2025)

Major vault protein inhibits CSFV replication by promoting cell apoptosis - Bihao Luo; Na Su; Yuehan Quan; Ning Li; Chen Chen; Liang Zhang; Lei Xu; Kangkang Guo (Veterinary Microbiology, 2025)

Sesame pods derived high-efficiency demulsifier: Synthesis and demulsification performance in oily wastewater treatment - Dou Wang; Jianle Li; Yongzhi Liu; Na Guo; Qingwen Qin (Process Safety and Environmental Protection, 2025)

Newly discovered Late Paleolithic sites in the southeastern margin of the Badain Jaran Desert, northwest China - Lu Teng; Xuefeng Sun; Hui Liu; Na Zhao; Shuangwen Yi; Feng Li; Xiaoqi Guo; Yuan Yao; Yinghua Wang; Christopher J. Bae; Huayu Lu (Quaternary Science Reviews, 2025)

Unveiling regulatory network of porcine oocyte IVM using integrated multi-omics - Yufen Jiang; Helin Li; Na Cheng; Yuchen Han; Qiue Xu; Mingjin Li; Muhammad Ameen Jamal; Jianxiong Guo; Honghui Li; Hong-Jiang Wei; Wenmin Cheng (Livestock Science, 2025)

Elucidating flavor compounds in Chinese steamed bread via glutinous rice wine-fermented dough technique: A triangulated analysis combining electronic tongue, SPME-GC-MS, and quantitative descriptive analysis - Jia-Xuan Li; Feng-Ping Qin; Meng-Ting Chen; Yu-Yu Liu; Xiao-Na Guo; Ke-Xue Zhu; Fei Gao; Jun-Jie Xing (Food Bioscience, 2025)

Can government supervision ensure compliance by photovoltaic enterprises? An evolutionary game analysis - Na Li; Tao Lv; Yuxia Guo; Jie Xu; Xiuzhu Zang; Jianli Guo; Mengyue Li (Energy Policy, 2025)

Intersite metal-metal interactions in Cu Fe diatomic single-atom pairs coordinated with S and N-ligands for efficient oxygen reduction reaction and rechargeable zinc-air batteries - Huihui Wang; Na Li; Zhen Meng; Jiangdu Huang; Dingrong Qiu; Kaijiong Guo; Li Jinxin; Dayong Fan; Vanchiappan Aravindan; Huidan Lu; Yongping Liu; Sundaram Chandrasekaran (Chemical Engineering Journal, 2025)

Bi-directional pH-responsive cellulose nanocrystals-based pesticide microcapsules for sustainable agriculture - Jia-wei Ding; Li-na Guo; Shu-heng Li; Qin Gao; Wang Wu; De-qiang Li; Jun Li (Carbohydrate Polymers, 2025)

Fluxgate Aeromagnetic Correction Based on Machine Learning-based and Data-Driven Approach - Li-zhong Xu; Gang Qiu; Nan Zhang; Li-na Guo; Hao Wang; Hua Guo (Applied Geophysics, 2025)

Breaking through the bottleneck of nitrogen pollution control in micropolluted water sources: Enhancement of aerobic denitrification efficacy driven by microbial community enrichment and its sustainable application - Honghong Guo; Yuhang Su; Shuhong Xue; Na Li; Rong Li; Sen Wang; Jianwei Bu; Haihan Zhang; Tinglin Huang (Water Research, 2025)

Systematic experiments and a multi-criteria assessment framework to validate amendments-enhanced agglomerated matrix layer for green roof stormwater and pollutant control - Wending Huang; Yimi Huang; Wuhu Guo; Shaoye Du; Junpeng Li; Jian Zhan; Xin Li; Yuxin Li; Yinglong Shen; Ya Wang; Yanqi Liu; Yuejin Chen; et al. (Journal of Cleaner Production, 2025)

Preparation high-efficiency NH2-MIL-125@g-C3N4 NADH photo-regeneration catalyst for enzymatic conversion of furfural to furfural alcohol - Shuaizhe Li; Xingyong Li; Senshen Yu; Qingtao Wang; Na Liu; Yichen Nie; Xuexiang Fu; Mengke Dong; Haolin Li; Yanliang Guo; Phidsavard Keomeesay; Shijie Liu; et al. (Journal of Environmental Chemical Engineering, 2025)

Mechanism of the effect of digested ovalbumin peptides on the calcium bioaccessibility of eggshell: Peptideomics and molecular docking - Xiaoxing Guo; Na Li; Xueying Wan; Ruitian Li; Nan Li; Xinhui Zhu; Jing Wang (Food Bioscience, 2025)

Exploring the anti-Listeria monocytogenes mechanisms of the postbiotics derived from Ligilactobacillus salivarius LSA-6 and its biopreservative effects on Inner Mongolian cheese - Ce Shi; Li Jia; Jinlong Xu; Na Guo; Haiying Cui; Tariq Aziz; Abdulhakeem S. Alamri; Walaa F. Alsanie; Majid Alhomrani; Changzhu Li; Lin Lin (Food Bioscience, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

UAV-based fine-scale daily relationship characterization between 3D urban surface thermal dynamics and landscape patterns - Rongyuan Dai; Fengxiang Guo; Han Zhao; Linshan Zhong; Chunyu Zhu; Na Ta; Hongqing Li; Qiong Wu (Sustainable Cities and Society, 2025)

Evaluation of ecological risks of antibiotics in Danjiangkou Reservoir basing on toxicity potency and antibiotic resistance genes transfer - Ruiwen Li; Yindan Zhang; Shuyin Li; Shan Chen; Chengchen Huang; Lihua Yang; Na Zheng; Yongyong Guo; Jian Han; Bingsheng Zhou; Yingcai Wang (Science of The Total Environment, 2025)

Polystyrene microplastic pollution induces species-specific shifts in root traits and rhizosphere conditions in a temperate forest - Yingtong Zhou; Wei Guo; Ivano Brunner; Jiaxin Liu; Xiaoyue Na; Qinrong Tang; Junni Wang; Cunguo Wang; Mai-He Li (Journal of Hazardous Materials, 2025)

CircRNA hsa_ circ_0009022 inhibits colorectal cancer progression by sponging miR-576–5p and complexing with FMRP - Jingyu Guo; Yongxia Wang; Yang Yang; Shuang Feng; Jinlong Cai; Shangqian Fan; Jingnan Wang; Na Li; Xinlai Qian; Huifang Zhu (Tissue and Cell, 2025)

(±)-Laevigiol A, a pair of new enantiomeric phenylpropanoids from the leaves and twigs of Croton laevigatus Vahl. and their anti-Alzheimer’s disease activities - Yu-Bin Lu; Mi-Na Yang; Hui-Jie Li; Li-Jia Ye; Le-Le Guo; Miao Zhang; Chun-Min Liu; Xin Wang; Yi-Nan Yang; Zhan-Xin Zhang; Dong-Qing Fei (Phytochemistry Letters, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

Photoaged polystyrene nanoplastics induce perturbation of glucose metabolism in HepG2 cells via oxidative stress - Ning Wang; Xin Zhu; Zhiqiang Xu; Xia Ning; Lin Guo; Dong Liang; Guangke Li; Na Zhu (Environmental Pollution, 2025)

A novel multi-functional PVA- alginate hydrogel with dynamic bond crosslinking for infected wound repair - Huanghe Zeng; Lingling Tang; Li Huang; Na Yang; Xingyue Chen; Xi Peng; Zhengxian Chen; Jianxiu Guo; Jie Weng; Tailin Guo (Carbohydrate Polymers, 2025)

Degradation of organic pollutant by natural biofilm based biophotovoltaic cells: The combined role of illumination, reactive oxygen species, and enhanced electron transfer - Zihan Qi; Xiuyi Hua; Anfeng Li; Haiyang Liu; Deming Dong; Dapeng Liang; Zhiyong Guo; Na Zheng (Bioresource Technology, 2025)

CD73 polymorphisms are associated with schizophrenia - He-Xia Peng; Li-Li Zhang; Dan Jiang; Na Jian; Ting-Mei Zhang; Jia-Guo Luo; Hai-Yan Yin (Purinergic Signalling, 2025)
Ecto-5’-nucleotidase/CD73 enzyme plays a key role in the regulation of extracellular adenosine levels, thereby exerting influence on adenosine homeostasis. Emerging evidence suggests that perturbations in purines and ecto-5’-nucleotidase activity are associated with an augmented susceptibility to schizophrenia. However, the precise impact of genetic variations in CD73 on individuals with schizophrenia remains poorly understood. Here, our study demonstrated that rs3734442 allele and rs4431401 heterozygote were conferred a significant risk of schizophrenia disease (rs3734442: odds ratio, 0.556; 95% CI, 0.375 to 0.825; p = 0.004; rs4431401: odds ratio, 1.881, 95% CI, 1.117 to 3.166; p = 0.020). Comparing different genders, we observed a significant association between rs3734442 genotypes and male cases (rs3734442: odds ratio, 0.452; 95% CI, 0.257 to 0.796; p = 0.007). Likewise, there was a significant association between rs4431401 genotypes and male patients (rs4431401: odds ratio, 2.570; 95% CI, 1.196 to 5.522; p = 0.015). Based on family history and antipsychotics medication usage, our data reveals that the rs9444348 allele exhibits the most significant association with familial susceptibility to schizophrenia (odds ratio, 1.541; 95% CI, 1.009 to 2.353; p = 0.048 for A vs G). Moreover, individuals carrying variants of rs6922, rs2229523, and rs2065114 while being treated with clozapine demonstrate a higher frequency proportion compared to those receiving risperidone treatment ( p = 0.035; p = 0.049; p = 0.027 respectively). Additionally, our results indicate that patients with GG genotype of rs9444348 had significantly higher likelihood of using clozapine instead of sulpiride ( p = 0.048). Overall, our data strongly suggest that genetic variations in CD73 are significantly associated with schizophrenia risk and may serve as valuable resources for identifying therapeutic targets.

Pannexin1 via P2rx7/amphiregulin contributes to cardiac fibrosis post myocardial infarction - Na Deng; Liwei You; Haijun Guo; Yingying Wei; Fujia Xu; Dandan Chen; Sihan Luo; Surong Huang; Siying Zuo; Wei Li; Xiaoyun Si (Journal of Molecular Histology, 2025)

Combined genome and transcriptome provides insight into the genetic evolution of an edible halophyte Suaeda salsa adaptation to high salinity - Bing Cui; Ranran Liu; Qiong Yu; Jianrong Guo; Xihua Du; Zixin Chen; Chenyang Li; Tong Wang; Ru Liu; Rui He; Congcong Song; Yue Liu; et al. (Molecular Ecology, 2025)
Suaeda salsa L. is a typical halophyte with high value as a vegetable. Here, we report a 447.98 Mb, chromosomal‐level genome of S. salsa , assembled into nine pseudomolecules (contig N50 = 1.36 Mb) and annotated with 27,927 annotated protein‐coding genes. Most of the assembled S. salsa genome, 58.03%, consists of transposable elements. Some gene families including HKT1 , NHX , SOS and CASP related to salt resistance were significantly amplified. We also observed expansion of genes encoding protein that bind the trace elements Zn, Fe, Cu and Mn, and genes related to flavonoid and α‐linolenic acid metabolism. Many expanded genes were significantly up‐regulated under salinity, which might have contributed to the acquisition of salt tolerance in S. salsa . Transcriptomic data showed that high salinity markedly up‐regulated salt‐resistance related genes, compared to low salinity. Abundant metabolic pathways of secondary metabolites including flavonoid, unsaturated fatty acids and selenocompound were enriched, which indicates that the species is a nutrient‐rich vegetable. Particularly worth mentioning is that there was no significant difference in the numbers of cis ‐elements in the promoters of salt‐related and randomly selected genes in S. salsa when compared with Arabidopsis thaliana , which may affirm that plant salt tolerance is a quantitative rather than a qualitative trait in terms of promoter evolution. Our findings provide deep insight into the adaptation of halophytes to salinity from a genetic evolution perspective.

Multi-Parameter Analysis of Stress Accumulation and Evolution Prior to the 2020 Guye MS5.1 Earthquake, North China: Insights from Apparent Stress, b-value, and Focal Mechanism Consistency - Xu-dong Ma; Lei Guo; Li-na Sun; Yi Zhou; Zhi-hua Ding (Applied Geophysics, 2025)

Multivariate model for predicting crop fluorine content based on soil physicochemical properties and fluorine speciation - Boxin Feng; Liming Gan; Qianni Men; Jiufen Liu; Yixin He; Na Guo; Tao He; Xiao Wang; Ronghua Li; Yajun Han (Environmental Monitoring and Assessment, 2025)

Adaptive modeling method integrating slime mould algorithm and cascade ensemble: Nondestructive detection of silage quality under VIS-NIRS - Kai Zhao; Haiqing Tian; Jue Zhang; Li’na Guo; Yang Yu; Haijun Li (Computers and Electronics in Agriculture, 2025)

Mechanisms and pollution characteristics of heavy metal flow in China's non-ferrous metal industry - Na Li; Zhenjiang Guo; Chengkang Gao; Huan You; Huijing Zhou; Xinhong Zhang; Tao Zheng (Journal of Cleaner Production, 2025)

Intergenerational inequity from hydrological drought in a warming world - Rutong Liu; Kebing Chen; Jiabo Yin; Biqiong Wu; Yan Zhao; Zhiming Liang; Na Li; Fengxian Gao; Jing Tian; Yujie Zeng; Jiali Guo (Journal of Environmental Management, 2025)

Flavor enhancement of soy protein isolate hydrolysates through the Maillard reaction and identification of saltiness-enhancing peptides - Hongbo Yi; Jun Li; Peng Wang; Shengnan Wang; Xiaofei Guo; Danshi Zhu; He Liu; Na Zhang (Food Bioscience, 2025)

Spatial distribution analysis of secondary metabolites in bolted and unbolted Saposhnikovia divaricata by atmospheric pressure laser ablation carbon fiber ionization mass spectrometry imaging - Na Li; Xialian Cui; Yingjie Lu; Fang Zhang; Su Guo; Yue Su; Yinlong Guo (Analytica Chimica Acta, 2025)

Discovery of isopentenyl flavonoids with inhibitory activity against hepatocellular carcinoma cells based on DeepSAT - Qing Wang; Ben‐Song Xin; Wen-Long Kou; Li-Na Gao; Gu-Xue Zhang; Yan-Jiao Qiao; Guo‐Dong Yao; Xiao‐Xiao Huang; Shao‐Jiang Song (Phytochemistry, 2025)

Mechanism of fatty acid synthesis metabolism during tuber swelling period of Chinese yam - Na Li; Yanfang Zhang; Xiuwen Huo; Shuchun Guo; Ningning Suo; Ye Tang (Food Chemistry, 2025)

Impact of fermentation duration in fermented glutinous rice wine dough procedure on the staling of Chinese steamed bread - Jia-Xuan Shang; Jia-Xuan Li; Feng-Ping Qin; Yi-Peng Bai; Xiao-Na Guo; Ke-Xue Zhu; Jun-Jie Xing (Food Bioscience, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Prediction of Lithium Mineralization Potential in the Jiulong Area, Western Sichuan (China), Using Spectral Residual Attention Convolutional Neural Network - Haiyang Luo; Na Guo; Chunhao Li; Hang Jiang (Natural Resources Research, 2025)

A nine-year study: continuous application of biochar achieves efficient potassium supply by modifying soil clay mineral composition and its potassium adsorption sites - Hangming Guo; Zhengchao Wu; Jiaxin Li; Zonglin Lu; Shuxiao Luan; Shixin Hu; Xingyu Liu; Na Li; Xiaori Han (Journal of Soils and Sediments, 2025)

Nutrient deficiency-induced downregulation of SNX1 inhibits ferroptosis through PPARs-ACSL1/4 axis in colorectal cancer - Li-Heng Qian; Kai-Ling Wen; Ying Guo; Ying-Na Liao; Ming-Yue Li; Zuo-Qing Li; Shu-Xin Li; Hui-Zhen Nie (Apoptosis, 2025)

Fate and transformation of psychotropic drugs in urban wastewater systems and receiving rivers via the integration of targeted and suspect screening analysis - An-Guo Wang; Jin-Na Zhang; Li-Xin Hu; You-Sheng Liu; Guang-Guo Ying; Yin-Xiu Liang; Mei-Ying Xu; Zhi-Qiang Yu (Water Research, 2025)

Associations of multiple metals exposure with immunoglobulin levels in pregnant women: Hangzhou Birth Cohort Study - Jiena Zhou; Lanfei Jin; Yexinyi Zhou; Kunhong Zhong; Kegui Huang; Qi Zhang; Jun Tang; Xue Zhang; Lihe Peng; Shuai Li; Na Lv; Dongdong Yu; et al. (Journal of Environmental Sciences, 2025)

Exploration of energy-saving processes for the separation of tetrahydrofuran/methanol/water: From separation mechanism to experimental validation - Jiahui Zhang; Chao Pan; Chunxiao Ren; Chuanxi Li; Shiying Di; Siqi Jiang; Qizhong Huang; Na Gao; Ningning Wang; Kuo Chang; Lingcong Kong; Zhiyuan Wang; et al. (Fuel, 2025)

Urban heat health risk inequality and its drivers based on local climate zones: A case study of Qingdao, China - Fei Guo; Guining Fan; Jun Zhao; Hongchi Zhang; Jing Dong; Hui Ma; Na Li (Building and Environment, 2025)

Physiological and transcriptomic responses of the microalga Isochrysis galbana during exposure to Hg(II) stress - Linlin Zhang; Na Li; Xinfeng Xiao; Linke Guo; Wenfang Li; Yanjun Li; Fei Ling (World Journal of Microbiology and Biotechnology, 2025)

Exosomes secreted from M2-polarized macrophages inhibit osteoclast differentiation via CYLD - Zi-yan Guo; Nan-nan Yin; Xiao-fei Li; Meng-meng Wang; Xiao-na Sui; Cai-di Jiang; Ming-hua Xu; Xiao-e Jia; Chong-jian Fu; Tie-lou Chen; Xin Liu (Tissue and Cell, 2025)

The integrating optional energy band alignment and oxygen vacancies over α/β-Fe2O3-3R homogenic boundary boosted self-fenton degradation of antibiotics - Jing Yan; Shi-Xian Guan; Ying Li; Jing Guo; Na Zhang; Jian-Yong Zhang; Chun-Wei Guo; Jie Ren; Qin-Fei Ke; Yong-Zheng Fang; Rui Zhang (Journal of Environmental Chemical Engineering, 2025)

Nomogram for Predicting Long-term Outcomes of Encephaloduroarteriosynangiosis in Toddlers with Moyamoya Disease: a Longitudinal and Cross-sectional Study - Qingbao Guo; Yan-Na Fan; Qian-Nan Wang; Jingjie Li; Cong Han; Zhengxing Zou; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; et al. (Translational Stroke Research, 2025)

Identification and validation of a major QTL, QFhb-6AL, for Fusarium head blight resistance on chromosome 6AL in wheat - Zhenzhen Zhu; Xuecheng Zhu; Na Zhang; Wenxi Wang; Jilu Liu; Fuping Zhang; Xiaomeng Ren; Yanpeng Ding; Fangyao Sun; Xi He; Sijia Hu; Xiuhua Li; et al. (Theoretical and Applied Genetics, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Deciphering the antibiotic resistome in stratified source water reservoirs in China: Distribution, risk, and ecological drive - Honghong Guo; Rong Li; Yuhang Su; Shuhong Xue; Na Li; Fan Chen; Xuanzi Zhangsun; Haihan Zhang; Xiaoyan Liu; Tinglin Huang (Journal of Hazardous Materials, 2025)

Saltiness perception enhancement of myofibrillar protein gel via microwave treatment: Microwave promotes protein aggregation - Na Luo; Jun Xiang; Bimal Chitrakar; Die Li; Yuxia Jin; Chaofan Guo; Xingwei Wang; Jianxin Cao; Xuejiao Wang (Innovative Food Science & Emerging Technologies, 2025)

The effect of soil depth on stoichiometry was greater than that of elevation in Abies georgei var. Smithii forest in Southeastern Tibet, China - Si-jie Zhu; Jiang-rong Li; Bo Zhang; Fang-wei Fu; Liang-na Guo (Acta Oecologica, 2025)

T-2 toxin triggers immunotoxic effects in goats by inducing ferroptosis and neutrophil extracellular traps - Jing Huang; Kaifeng He; Xin Guo; Jiaxuan Wang; Han Hu; Xuhui Zhang; Na Guo; Yiwen Wang; Wenlong Huang; Rongsheng Huang; Tingting Liu; Xi Jiang; et al. (Toxicology and Applied Pharmacology, 2025)

Dual lipases immobilized on magnetic hydrophobic biochar for one-step production of biodiesel in deep eutectic solvent - Jing-jing Guo; Li Wang; Yi-tong Wang; Wo-na Ding; Wei-wei Liu; Zhen Fang (Fuel, 2025)

Effects of sodium chloride on the textural attributes, rheological properties, microstructure, and 3D printing performance of rice starch-curdlan composite gel - Weixian Li; Kangning Zhang; Yang Qin; Man Li; Hongyan Li; Minqiang Guo; Tongcheng Xu; Qingjie Sun; Na Ji; Fengwei Xie (Food Chemistry, 2025)

Antifungal activities of Pediococcus pentosaceus LWQ1 and Lactiplantibacillus plantarum LWQ17 isolated from sourdough and their efficacies on preventing spoilage of Chinese steamed bread - Xueying Wu; Yongxin Liu; Zhengli Guo; Na Ji; Qingjie Sun; Tongjie Liu; Yang Li (Food Control, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Considerable declines in odor in a drinking water reservoir: Variations of odorous community, precursor enzymes abundance, distribution, and environmental dominant factors - Honghong Guo; Rong Li; Shuhong Xue; Xuanzi Zhangsun; Daojun Huang; Yongchao Li; Na Li; Yuhang Su; Haihan Zhang; Tinglin Huang (Water Research, 2025)

Investigating the application of multiple-stage fermented glutinous rice procedure in dough preparation for Chinese steamed bread - Jia-Xuan Li; Jia-Xuan Shang; Feng-Ping Qin; Xiao-Na Guo; Ke-Xue Zhu; Jun-Jie Xing (Food Bioscience, 2025)

Research progress and hot topics of distributed photovoltaic: Bibliometric analysis and Latent Dirichlet Allocation model - Na Li; Tao Lv; Xingyu Wang; Xiangyun Meng; Jie Xu; Yuxia Guo (Energy and Buildings, 2025)

Investigating the mechanism of auxin-mediated fulvic acid-regulated root growth in Oryza sativa through physiological and transcriptomic analyses - Yi Tang; Ke Chen; Yanan Guo; Tianrui Li; Na Kuang; Zhixuan Liu; Haona Yang (Planta, 2025)

Rice rhizosphere microbiome is more diverse but less variable along environmental gradients compared to bulk soil - Yaping Guo; Yakov Kuzyakov; Na Li; Bin Song; Zihao Liu; Jonathan M. Adams; Lin Yang (Plant and Soil, 2025)

Navβ2 Intracellular Fragments Contribute to Aβ1-42-Induced Cognitive Impairment and Synaptic Deficit Through Transcriptional Suppression of BDNF - Min-Nan Lu; Dan Wang; Chen-Jun Ye; Guo-Ji Yan; Jing-Feng Song; Xin-Ying Shi; Shan-Shan Li; Li-Na Liu; Hui-Xiang Zhang; Xiao-Han Dong; Tao Hu; Xu-Yang Wang; et al. (Molecular Neurobiology, 2025)

Attribution analysis of trends in reference crop evapotranspiration in China - Yue Liu; Mengjing Guo; Jing Li; Na Lyu; Junqi Zhang; Bowen Zhang (Journal of Geographical Sciences, 2025)

Development of a PCR assay for detection and identification of Eimeria spp. in cattle - Xuehua Chen; Miner Deng; Nan Chen; Xiaohong Chen; Na Li; Yaoyu Feng; Lihua Xiao; Yaqiong Guo (Veterinary Parasitology, 2024)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Fully biobased unsymmetric bisphenols from condensation of lignin-derived monophenols for non-isocyanate polyurethane synthesis - Na Shi; Yongwei Ni; Zhenjiang Li; Kai Chen; Daiqing Zhou; Min Zhang; Weizhou Huang; Yujia Wang; Ming Chen; Kai Guo (Fuel, 2024)

The effects of different cooking methods on nutrients, bioactive components and antioxidant activities of Naematelia aurantialba were revealed by simulating in vitro digestion - Guangzhi Li; Xin Wang; Zhiguo Na; Weiye Xiu; Jingyang Wang; Ying Guan; Jinjin Guo; Yongqiang Ma (Food Research International, 2024)

Two new furanone derivatives from the endophytic fungus Byssochlamys sp. and their cytotoxic activities - Jie Wang; Wen-Bin Gao; Fan-Wei Liu; Qi Liu; Bo Song; Jin Ye; Ying Chen; Cai-Lin Zhao; Wei Dong; Li-Na Guo; Bo Song (Natural Product Research, 2024)

Numerical Simulation of the Horizontal Water-Entry Process of High-Speed Vehicles - Jin-Long Ju; Na-Na Yang; Yi-Fei Zhang; Lei Yu; Zhe Zhang; Liang-Chao Li; Guo-Lu Ma; Wen-Hua Wu (Journal of Marine Science and Engineering, 2024)
Based on the RNG k-ε turbulence model and VOF multiphase flow model, a numerical model of horizontal water-entry of the vehicle was established, and the numerical method was verified by experimental results. The cavitation characteristics, fluid resistance, and motion of the vehicle under different conditions were studied during the vehicle’s water-entry process. The results show that the cavitation process can be divided into the cavity development stage, saturation stage, and collapse stage. With the increase in initial velocity and mass of the vehicle, more water vapor will be generated during the water-entry process. The initial velocity of the vehicle had a limited effect on the resistance coefficient. The resistance coefficient in the stable stage remained almost unchanged for vehicles with different masses. Nevertheless, the time interval of the stable stage was shortened, and the resistance coefficient was greater in the gradually increasing stage for the vehicle with a smaller mass. For vehicles with higher initial velocity or smaller mass, the instantaneous velocity decreased faster after it entered the water. The vehicle with a streamlined design was able to reduce the generation of water vapor and decrease fluid resistance and its coefficient, and the vehicle can run farther during the water-entry process.

Trajectory of antibiotic resistome response to antibiotics gradients: A comparative study from pharmaceutical and associated wastewater treatment plants to receiving river - Na Wang; Shuchang Li; Mali Shi; Ni Ni; Xiaohui Zhang; Xinyan Guo; Huai Lin; Yi Luo (Water Research, 2024)

Glyphosate-based herbicides reduced overwintering population and reproduction of agrobiont spiders - Na Yu; Jingjing Li; Yunru Chen; Yunchao Wang; Zonglei Guo; Zewen Liu (Journal of Hazardous Materials, 2024)

Spatial and temporal dynamics of microbes and genes in drinking water reservoirs: Distribution and potential for taste and odor generation - Xuanzi Zhangsun; Honghong Guo; Quanjie Du; Na Li; Shuhong Xue; Rong Li; Wenrui Ma; Xiang Liu; Haihan Zhang; Tinglin Huang (Journal of Hazardous Materials, 2024)

Synergistic implementation of efficient adsorption-diffusion-conversion in lithium-sulfur batteries via built-in electric field constructed by transition metal selenides - Jun Wang; Kai Huang; Qi Li; Guo Cheng; Yongzheng Zhang; Na Teng; Cheng Lian; Cheng Ma; Jitong Wang; Wenming Qiao; Licheng Ling (Chemical Engineering Journal, 2024)

Design of dual-defective polymeric carbon nitride with compact interlayer stacking for boosting photocatalytic H2O2 production: Insight of various configurations - Binrong Li; Na Li; Zhiwei Guo; Chen Wang; Xuedong Wang; Zhi Zhu; Xu Tang; Pengwei Huo (Chemical Engineering Journal, 2024)

Effect of powder activated carbon (PAC) addition on the performance of anaerobic dynamic membrane bioreactor (AnDMBR): Stratification analysis of dynamic membrane characteristics - Yuqi Sun; Qingyang Guo; Wenkai Rao; Na Li; Yuxin Bai; Jian Zhang; Shuang Liang (Chemical Engineering Journal, 2024)

Co-production of plant- and microbial- proteins from waste tobacco leaves by optimizing alkaline extraction and strengthening pectin bioconversion - Yingjie Guo; Guodong Liu; Sulei Li; Na Chen; Zhongfeng Zhang; Peng Zhang; Liwei Gao (Bioresource Technology, 2024)

Investigating the Effects of Perampanel on Autophagy-mediated Regulation of GluA2 and PSD95 in Epilepsy - Dan Li; Na Sun; Yingying Guo; Shaoping Huang; Chunyan Yin; Yanfeng Xiao; Weijun Ma (Molecular Neurobiology, 2024)

Design of enhanced entropy-driven non-covalent DNA catalytic reactions via the paired junction structure - Weitao Wang; Hongyan Yu; Xiaole Han; Li Zhang; Zhi Weng; Chen Zuo; Na Yin; Yaoyi Zhang; Tong Feng; Dan Bai; Ao Tang; Yongcan Guo; et al. (Chemical Engineering Journal, 2024)

Enhancing nitrogen removal in source water with intermittent aeration: Improved performance of iron-reducing denitrifying bacteria - Honghong Guo; Na Li; Shuhong Xue; Xuanzi Zhangsun; Tinglin Huang; Haihan Zhang; Ben Ma (Chemical Engineering Journal, 2024)

Transformation of mulberry polyphenols by Lactobacillus plantarum SC-5: Increasing phenolic acids and enhancement of anti-aging effect - Mengyao Li; Xiangxiu Xu; Yifan Jia; Yuan Yuan; Guo Na; Ling Zhu; Xiaowei Xiao; Yamin Zhang; Haiqing Ye (Food Research International, 2024)

Impacts of non-linear ITRF2020 on reference frame alignment - Guo Chen; Na Wei; Hao Wang; Tao Li; Min Li; Qile Zhao (Advances in Space Research, 2024)

The jasmonate pathway promotes nodule symbiosis and suppresses host plant defense in Medicago truncatula - Da Guo; Jingrui Li; Peng Liu; Yuzhan Wang; Na Cao; Xiangling Fang; Tao Wang; Jiangli Dong (Molecular Plant, 2024)

A degradable multi-functional packaging based on chitosan/silk fibroin via incorporating cellulose nanocrystals-stabilized cinnamon essential oil pickering emulsion - Jian-Dong Wang; Shi-Liang Yang; Guo-Sheng Liu; Quan Zhou; Li-Na Fu; Qi Gu; Zi-Hui Cai; Su Zhang; Yu-Jie Fu (Food Hydrocolloids, 2024)

L-Alanine promotes anti-infectious properties of Bacillus subtilis S-2 spores via the germination receptor gerAA - Shuang Lu; Xianying Liao; Wei Lu; Li Zhang; Kai Na; Xiangyu Li; Xiaohua Guo (Probiotics and Antimicrobial Proteins, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

Exploring the Roles of m6A-Modified circRNAs in Myasthenia Gravis Based on Multi-Omics Analysis - Shuang Li; Yu Zhang; Geyu Liu; Na Song; Zhe Ruan; Rongjing Guo; Yonglan Tang; Xiangqi Cao; Xiaoxi Huang; Ting Gao; Sijia Hao; Qingqing Wang; et al. (Molecular Neurobiology, 2024)

Effects of heating rate on upper thermal limit: insights from cardiac performance and transcriptomic response in mudflat snail Batillaria attramentaria - Li-Na Du; Ying-Hui Du; Guo-Dong Han (Frontiers in Marine Science, 2024)
Studying the effect of heating rate on upper thermal limit has gained considerable attention in enhancing our mechanistic understanding of how organisms respond to changing temperatures in the context of climate change. The present study aimed to investigate the effects of heating rate on upper thermal limit and understand the physiological and molecular mechanisms used by organisms to cope with thermal stress at different heating rates. Batillaria attramentaria snails were exposed to slow (3°C/h) or fast (9°C/h) heating rates. The median lethal temperature (LT 50 ) of snails exposed to these varying heating rates was determined. Additionally, we assessed heart rate under constant heating and investigated the transcriptomic response at the temperature where the heart rate reaches zero (FLT). The results revealed that snails exhibit a higher upper thermal limit (approximately 1.5°C) during fast heating as compared to slow heating. On average, the heart rate of slowly heated snails was 11 beats per minute lower than that of fast heated snails when the temperature was below 45°C. The findings indicate that the metabolic rate is lower during slow heating compared to fast heating when subjected to the same level of thermal stress. When exposed to a temperature of FLT, snails initiated a typical heat shock response to thermal stress, which included the increased expression of genes encoding heat shock proteins ( HSPs ) and protein disulfide isomerase ( PDIA5 ) involved in protein folding. Remarkably, the genes glucose-regulated protein 94 (GRP94) and Calnexin , which are associated with the binding of unfolded proteins, showed distinct up-regulation in snails that were heated slowly, indicating the accumulation of misfolded proteins. The accumulation of misfolded proteins, coupled with additional energy consumption, may contribute to the lower upper thermal limit observed at a slow heating rate. Our research provides valuable insights for determining the realistic upper limits of temperature tolerance and improving predictions of how organisms will be affected by climate change in the future.

Targeted and untargeted metabolomics reveals meat quality in grazing yak during different phenology periods on the Qinghai-Tibetan Plateau - Tongqing Guo; Qian Zhang; Xungang Wang; Xianli Xu; Yalin Wang; Lin Wei; Na Li; Hongjin Liu; Linyong Hu; Na Zhao; Shixiao Xu (Food Chemistry, 2024)

Sustained release of a novel bilayer packaging film loaded with binary microemulsion of melatonin/pummelo essential oil and its regulation of postharvest energy metabolism in Agaricus bisporus - Lei Feng; Na Zhang; Jia Wang; Xin Jiang; Jiali Han; Ling Li; Hiroaki Kitazawa; Xiangyou Wang; Cunkun Chen; Yanyin Guo (Food Control, 2024)

Understanding the effect of multiple configurations in polymeric carbon nitride for efficient solar-driven hydrogen peroxide photosynthesis - Binrong Li; Na Li; Zhiwei Guo; Chen Wang; Zhi Zhu; Xu Tang; Gabriel Andrew Penyikie; Xuedong Wang; Pengwei Huo (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Glucose dependent resistance associated with intestinal microbiota facilitate teleost to survive bacterial infection - Na Zhao; Yuting Liu; Jiamin Guo; Yubang Shen; Bo Zhang; Jiale Li (Aquaculture, 2024)

Ratiometric fluorescence platform for the ultrasensitive detection of kanamycin based on split aptamer co-recognition triggers Mg2+-DNAzyme-driven DNA walker systems - Xia Lu; Long Wang; Guowei Li; Yuxin Wang; Guo Hao; Yi Ding; Mengjia Liu; Shangchen Fu; Liqing Xu; Na Ge; Wupeng Ge (Science of The Total Environment, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Cell-Cycle-related Protein Centromere Protein F Deficiency Inhibits Cervical Cancer Cell Growth by Inducing Ferroptosis Via Nrf2 Inactivation - Xin hui Tang; Tian nan Zhao; Li Guo; Xin yue Liu; Wei na Zhang; Ping Zhang (Cell Biochemistry and Biophysics, 2024)
Cervical cancer (CC) is one of the severe cancers that pose a threat to women’s health and result in death. CENPF, the centromere protein F, plays a crucial role in mitosis by regulating numerous cellular processes, such as chromosome segregation during mitosis. According to bioinformatics research, CENPF serves as a master regulator that is upregulated and activated in cervical cancer. Nevertheless, the precise biological mechanism that CENPF operates in CC remains unclear. The aim of this study was to analyze the function of CENPF on cervical cancer and its mechanism. We conducted immunohistochemistry and western blot analysis to examine the expression levels of CENPF in both cervical cancer tissues and cells. To explore the hidden biological function of CENPF in cell lines derived from CC, we applied lentivirus transfection to reduce CENPF manifestation. CENPF’s main role is to regulate ferroptosis which was assessed by analyzing Reactive Oxygen Species (ROS), malonaldehyde (MDA), etc. The vitro findings were further validated through a subcutaneous tumorigenic nude mouse model. Our research finding indicates that there is an apparent upregulation of CENPF in not merely tumor tissues but also cell lines in the carcinomas of the cervix. In vitro and vivo experimental investigations have demonstrated that the suppression of CENPF can impede cellular multiplication, migration, and invasion while inducing ferroptosis. The ferroptosis induced by CENPF inhibition in cervical cancer cell lines is likely mediated through the Nrf2/HO-1 pathway. The data herein come up with the opinion that CENPF may have a crucial role in influencing anti-cervical cancer effects by inducing ferroptosis via the triggering of the Nrf2/HO-1 signaling pathway.

Methyl Jasmonate Treatment Relieves Chilling Injury and Improves the Postharvest Quality of Snap Bean by Regulating Antioxidant Metabolism - Na Lv; Li Li; Na Wang; Chang-jie Guo; Hao-yan Zhang (Agricultural Research, 2024)

FSN-YOLO: Nearshore Vessel Detection via Fusing Receptive-Field Attention and Lightweight Network - Na Du; Qing Feng; Qichuang Liu; Hui Li; Shikai Guo (Journal of Marine Science and Engineering, 2024)
Vessel detection is critical for ensuring maritime transportation and navigational safety, creating a pressing need for detection methodologies that are more efficient, precise, and intelligent in the maritime domain. Nonetheless, accurately detecting vessels across multiple scales remains challenging due to the diversity in vessel types and locations, similarities in ship hull shapes, and disturbances from complex environmental conditions. To address these issues, we introduce an innovative FSN-YOLO framework that utilizes enhanced YOLOv8 with multi-layer attention feature fusion. Specifically, FSN-YOLO employs the backbone structure of FasterNet, enriching feature representations through super-resolution processing with a lightweight Convolutional Neural Network (CNN), thereby achieving a balance between processing speed and model size without compromising accuracy. Furthermore, FSN-YOLO uses the Receptive-Field Attention (RFA) mechanism to adaptively fine-tune the feature responses between channels, significantly boosting the network’s capacity to capture critical information and, in turn, improve the model’s overall performance and enrich the discriminative feature representation of ships. Experimental validation on the Seaship7000 dataset showed that, compared to the baseline YOLOv8l approach, FSN-YOLO considerably increased accuracy, recall rates, and mAP@0.5:0.95 by absolute margins of 0.82%, 1.54%, and 1.56%, respectively, positioning it at the forefront of current state-of-the-art models.

Sequence introgression from exogenous lineages underlies genomic and biological differences among Cryptosporidium parvum IOWA lines - Wanyi Huang; Kevin Tang; Chengyi Chen; Michael J. Arrowood; Ming Chen; Yaqiong Guo; Na Li; Dawn M. Roellig; Yaoyu Feng; Lihua Xiao (Water Research, 2024)

Non-negligible impact of microplastics on wetland ecosystems - Na-ying Li; Bo Zhong; Yun Guo; Xian-xiang Li; Zao Yang; Yi-xin He (Science of The Total Environment, 2024)

Risk assessment of broflanilide for human and non-target terrestrial organisms in cauliflower production - Hongfang Lin; Yuanping Yang; Na Li; Siyu Liu; Lijing Yang; Yu Cheng; Huishan Sheng; Hui Li; Wanting Wen; Yongze Guo; Yuting Zhang (Environmental Research, 2024)

Author Correction: Porphyromonas gingivalis promotes the progression of oral squamous cell carcinoma by stimulating the release of neutrophil extracellular traps in the tumor immune microenvironment - Zhi-chen Guo; Si-li Jing; Xin-yu Jia; Sadam Ahmed Elayah; Lin-yang Xie; Hao Cui; Jun-bo Tu; Si-jia Na (Inflammation Research, 2024)

Porphyromonas gingivalis promotes the progression of oral squamous cell carcinoma by stimulating the release of neutrophil extracellular traps in the tumor immune microenvironment - Zhi-chen Guo; Si-li Jing; Xin-yu Jia; Sadam Ahmed Elayah; Lin-yang Xie; Hao Cui; Jun-bo Tu; Si-jia Na (Inflammation Research, 2024)

MicroRNA-322-5p targeting Smurf2 regulates the TGF-β/Smad pathway to protect cardiac function and inhibit myocardial infarction - Liping Guo; Ke Li; Yan Ma; Huaiming Niu; Jun Li; Xin Shao; Na Li; Yuehui Sun; Haixiong Wang (Human Cell, 2024)

A new strategy to stabilize the heavy metals in carbonized MSWI-fly ash using an acid-resistant oligomeric dithiocarbamate chelator - Bojun Li; Xuejun Guo; Xiangyuan Zhang; Siwen Leng; Na Ma; Xiaoqiong Wu (Journal of Hazardous Materials, 2024)

Ce enhanced low-temperature performance of Mn modified Cu-Beta zeolite catalyst for NH3-SCR - Xin Guo; Zhiyong Ding; Na Kang; Liu Yang; Yuanjiang Wang; Cheng Zhang; Zhaoqiang Li; Tiantian Zhang; Yan Wang; Yu Wang; Hao Qu (Fuel, 2024)

Dissolved Mn2+ promotes microbially-catalyzed protodolomite precipitation in brackish oxidized water - Zuozhen Han; Jie Li; Yanyang Zhao; Qingyuan Chen; Xiao Gao; Kaiming Hu; Na Guo; Xiangyu Wei; Ruirui Meng; Chenlin Zhu; Maurice E. Tucker; Chao Han (Chemical Geology, 2024)

Exploring the Protective Effect of Total Flavonoids from Semen Cuscutae on Ovarian Germline Stem Cells Based on Notch Signaling Pathway - Yuan Li; Hanqian Du; Jiashan Li; Zehui Li; Li Guo; Panyu Xu; Ying Xu; Na Lin (Stem Cell Reviews and Reports, 2024)

Experimental investigation on pillar rockburst of true triaxial four-face rapid unloading under high stress - Jieyu Li; Dongqiao Liu; Manchao He; Yunpeng Guo; Na Li; Jiamiao Zhang (Bulletin of Engineering Geology and the Environment, 2024)

Effects of three exogenous phytohormones on the growth, selenium absorption, and metabolism of the microalga Parachlorella kessleri under sodium selenite stress - Yuhao Guo; Yan Cao; Rundong Yang; Feifei Wang; Na Zhang; Shuyi Li; Zhenzhou Zhu (Algal Research, 2024)

Comparison and development of scanning electron microscope techniques for delicate plant tissues - Jinhong Yuan; Lin Yang; Panpan Yu; Na Tang; Le Liu; Wenke Wang; Pei Wang; Qingxiang Yang; Siyi Guo; Junhua Li (Plant Science, 2024)

Variations in microbial residue carbon and its contribution to soil organic carbon after vegetation restoration on farmland: The case of Guinan County - Na Li; Yalin Wang; Lin Wei; Xungang Wang; Qian Zhang; Tongqing Guo; Xianli Xu; Na Zhao; Shixiao Xu (Organic Geochemistry, 2024)

Removing refractory organic substances from landfill leachate using a nanofiltration membrane bioreactor: Performance and mechanisms - Chu Zhou; Na Li; Wenbin Guo; Rui Wang; Yaohua Yan; Senlin Shao (Chemical Engineering Journal, 2024)

Dual-pathway glycolysis inhibition for boosting bioenergetic therapy synergistic with chemodynamic/photothermal therapy - Pengxin Song; Renlu Han; Yun Gao; Zhen Guo; Xiangjun Wei; Na Li; Jiancheng Yu; Keqi Tang (Chemical Engineering Journal, 2024)

Bacillus -derived probiotics: metabolites and mechanisms involved in bacteria–host interactions - Shuang Lu; Kai Na; Yuanrong Li; Li Zhang; Ying Fang; Xiaohua Guo (Critical Reviews in Food Science and Nutrition, 2024)

Aggregation behavior of polystyrene nanoplastics: Role of surface functional groups and protein and electrolyte variation - Yihui Guo; Ning Tang; Lan Lu; Na Li; Tingting Hu; Jiayin Guo; Jingyi Zhang; Zhuotong Zeng; Jie Liang (Chemosphere, 2024)

Gemfibrozil Alleviates Cognitive Impairment by Inhibiting Ferroptosis of Astrocytes via Restoring the Iron Metabolism and Promoting Antioxidant Capacity in Type 2 Diabetes - Nan Wang; Yujing Zhao; Meiyan Wu; Na Li; Chaoying Yan; Hongyan Guo; Qiao Li; Qing Li; Qiang Wang (Molecular Neurobiology, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Knowledge evolution learning: A cost-free weakly supervised semantic segmentation framework for high-resolution land cover classification - Hao Cui; Guo Zhang; Yujia Chen; Xue Li; Shasha Hou; Haifeng Li; Xiaolong Ma; Na Guan; Xuemin Tang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Facile fabrication of regenerable spherical La0.8Ce0.2MnO3 pellet via wet-chemistry molding strategy for elemental mercury removal - Wei Zheng; Xingyue Zhou; Yuanyuan Na; Jianping Yang; Yingchao Hu; Qingjie Guo; Zequn Yang; Wenqi Qu; Lijian Leng; Hailong Li (Chemical Engineering Journal, 2024)

Transcriptome analysis and identification of the low potassium stress-responsive gene SiSnRK2.6 in foxtail millet (Setaria italica L.) - Xiaoqian Ma; Najeeb Ullah Khan; Shutao Dai; Na Qin; Zanping Han; Bing Guo; Junxia Li (Theoretical and Applied Genetics, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

A semi-analytical model to estimate Chlorophyll-a spatial-temporal patterns from Orbita Hyperspectral image in inland eutrophic waters - Zhubin Zheng; Chao Huang; Yunmei Li; Heng Lyu; Changchun Huang; Na Chen; Ge Liu; Yulong Guo; Shaohua Lei; Runfei Zhang; Jianzhong Li (Science of The Total Environment, 2023)

Exposure to copper induces endoplasmic reticulum (ER) stress-mediated apoptosis in chicken (Gallus gallus) myocardium - Feiyang Ma; Xinyan Ma; Fan Yang; Jianzhao Liao; Na Qiao; Wenlan Yu; Qingyue Han; Ying Li; Jiaqiang Pan; Lianmei Hu; Jianying Guo; Zhaoxin Tang (Veterinary Research Communications, 2023)

Protocol for Brain Magnetic Resonance Imaging and Extraction of Imaging-Derived Phenotypes from the China Phenobank Project - Chengyan Wang; Zhang Shi; Yan Li; Xueqin Xia; Xutong Kuang; Shufang Qian; Le Xue; Lizhen Lan; Yudan Wu; Na Zhang; Ji Tao; Xumei Hu; et al. (Phenomics, 2023)

Development and Evaluation of Real-Time Polymerase Chain Reaction (PCR) to Authenticate Sablefish ( Anoplopoma fimbria ) in Commercial Seafood Products - Meng Qu; Yanhua Jiang; Yingying Guo; Wenjia Zhu; Shufang Liu; Na Li; Fengling Li; Lin Yao; Zhijun Tan; Lianzhu Wang (Journal of Aquatic Food Product Technology, 2023)

Comparative assessment of food safety regulations and standards for arsenic, cadmium, lead, mercury and iodine in macroalgae used as food and feed in China and Europe - Yingying Guo; Anne-Katrine Lundebye; Na Li; Åshild Ergon; Shaojun Pang; Yanhua Jiang; Wenjia Zhu; Yanfang Zhao; Xiaodong Li; Lin Yao; Lianzhu Wang; Inger Aakre (Trends in Food Science & Technology, 2023)

Accumulation of microbial necromass carbon and its contribution to soil organic carbon in artificial grasslands of various vegetation types - Na Li; Na Zhao; Shixiao Xu; Yalin Wang; Lin Wei; Qian Zhang; Tongqing Guo; Xungang Wang (European Journal of Soil Biology, 2023)

Boosted zn-ion storage in high crystalline VS4 anode by enhanced diffusion-controlled kinetics - Cheng Zheng; Zhu Guo; Bangquan Jian; Zuochao Chen; Jiarui Zhong; Na Li; Shaoming Huang (Chemical Engineering Journal, 2023)

Enhanced nitrogen removal from micro-polluted water by Fe (II)/Fe (III) cycling under intermittent aeration - Honghong Guo; Na Li; Shuhong Xue; Xuanzi Zhangsun; Tinglin Huang; Haihan Zhang; Taixin Liu; Lei wang; Quanjie Du; Nan Li (Chemical Engineering Journal, 2023)

Enhanced nitrogen removal of micropolluted source waterbodies using an iron activated carbon system with siliceous materials: Insights into metabolic activity, biodiversity, interactions of core genus and co-existence - Honghong Guo; Xuanzi Zhangsun; Na Li; Xiang Liu; Haihan Zhang; Tinglin Huang (Bioresource Technology, 2023)

Leopard predation on wild Sichuan snub-nosed monkeys - Bin Yang; James R. Anderson; Ni-Na Gou; Jun Luo; Bo Hong; Wei-Wei Fu; Yong-Feng Chen; Wei-Feng Wang; Bao-Jia Cao; Shi-Yu Chen; Kai-Feng Wang; Bao-Guo Li (Primates, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Tigliane-and daphnane-type diterpenoids from the buds of Daphne genkwa with their cytotoxic activities - Ying Chen; Cai-Lin Zhao; Wei Dong; Fei-Fan Song; Li-Na Guo; Hong-Lian Zhang; Lv Zhen; Li Li; Jin Ye; Bo Song (Natural Product Research, 2023)

Integration of eQTL and GWAS analysis uncovers a genetic regulation of natural ionomic variation in Arabidopsis - Chaoqun Xu; Ling-Yu Song; Ying Zhou; Dong-Na Ma; Qian-Su Ding; Ze-Jun Guo; Jing Li; Shi-Wei Song; Lu-Dan Zhang; Hai-Lei Zheng (Plant Cell Reports, 2023)

CS-NO suppresses inhibits glycolysis and gastric cancer progression through regulating YAP/TAZ signaling pathway - Na Guo; Hongxuan Ma; Dehui Li; Huanfang Fan; Chunxia Sun; Yunchao Sun (Cell Biochemistry and Biophysics, 2023)

New α-pyrone and unsaturated ketone analogues from the endophytic fungus Lasiodiplodia sp. and their cytotoxic effects - Wei Dong; Wen-Bin Gao; Fan-Wei Liu; Jin-Ye; Ying Chen; Hong-Lian Zhang; Zhen Lv; Li-Na Guo; Bo Song (Phytochemistry Letters, 2023)

Dynamic Measurements of Cerebral Blood Flow Responses to Cortical Spreading Depolarization in the Murine Endovascular Perforation Subarachnoid Hemorrhage Model - Jin Yan; Wenlang Li; Chao Zhou; Na Wu; Xiaomin Yang; Qiuling Pan; Tao He; Yue Wu; Zongduo Guo; Yongzhi Xia; Xiaochuan Sun; Chongjie Cheng (Translational Stroke Research, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Rockfall feature investigation and kinematic simulation based on nap-of-the-object photogrammetry and GIS spatial modeling - Xude Li; Fu-zhen Liu; Li Zhao; Na Deng; Long Chen; Jing-shen Pan; Guo-qiang Tang (Natural Hazards, 2023)

Immune functions of the Dscam extracellular variable region in Chinese mitten crab - Xiao-Li Zhang; Guo-Qing Shen; Xiao-Na Zhang; Yue-Hong Zhao; Wei-Wei Li; Qun Wang (Fish & Shellfish Immunology, 2023)

Alginate oligosaccharide structures differentially affect DSS-induced colitis in mice by modulating gut microbiota - Shuang Lu; Kai Na; Jiani Wei; Ting Tao; Li Zhang; Ying Fang; Xiangyu Li; Xiaohua Guo (Carbohydrate Polymers, 2023)

Influence of crack characteristics on the morphological development of Benggang and hydrological processes - Wei-ping Liu; Shu-han Wang; Si-wen Tian; Guo-quan Ouyang; Li-na Hu; Zhi-jun Yuan (Journal of Mountain Science, 2023)

Evaluation of GPS and BDS-3 broadcast earth rotation parameters: a contribution to the ephemeris rotation error - Wenwen Li; Guo Chen; Min Li; Na Wei; Yubin Wang; Qile Zhao (GPS Solutions, 2023)

Enhancing pro-environmental behaviour of employees towards renovation waste for a circular economy: The role of external supervision and corporate environmental responsibility - Shiwang Yu; Jian Li Hao; Luigi Di Sarno; Wenting Ma; Na Guo; Yong Liu (Sustainable Chemistry and Pharmacy, 2023)

Ethylene carbonate generated efficiently via ethylene oxide and CO2 on the Li-MgO(1 0 0) surface based on the synergistic activation of bimetals without halogen - Yunya Guo; Jingjing Zhang; Na Sun; Lixia Ling; Riguang Zhang; Heqin Guo; Debao Li; Baojun Wang (Fuel, 2023)

Effects of bisphenols on lipid metabolism and neuro–cardiovascular toxicity in marine medaka larvae - Xueyou Li; Xiaoxu He; Xiaona Lin; Weihao Li; Jiahao Gao; Ning Zhang; Yusong Guo; Zhongduo Wang; Na Zhao; Bo Zhang; Zhongdian Dong (Aquatic Toxicology, 2023)

Upgrading the accumulation of ginsenoside Rd in Panax notoginseng by a novel glycosidase-producing endophytic fungus G11-7 - Lili Niu; Xiangyu Qin; Litao Wang; Na Guo; Hongyan Cao; Hanghang Li; Chunjian Zhao; Huimei Wang; Yujie Fu (Folia Microbiologica, 2023)

Quantifying the spatial nonstationary response of influencing factors on ecosystem health based on the geographical weighted regression (GWR) model: an example in Inner Mongolia, China, from 1995 to 2020 - Li Na; Yu Shi; Luo Guo (Environmental Science and Pollution Research, 2023)
The identification of ecosystem health and its influencing factors is crucial to the sustainable management of ecosystems and ecosystem restoration. Although numerous studies on ecosystem health have been carried out from different perspectives, few studies have systematically investigated the spatiotemporal heterogeneity between ecosystem health and its influencing factors. Considering this gap, the spatial relationships between ecosystem health and its factors concerning climate, socioeconomic, and natural resource endowment at the county level were estimated based on a geographically weighted regression (GWR) model. The spatiotemporal distribution pattern and driving mechanism of ecosystem health were systematically analysed. The results showed the following: (1) the ecosystem health level in Inner Mongolia spatially increases from northwest to southeast, displaying notable global spatial autocorrelation and local spatial aggregation. (2) The factors influencing ecosystem health exhibit significant spatial heterogeneity. Annual average precipitation (AMP) and biodiversity (BI) are positively correlated with ecosystem health, and annual average temperature (AMT) and land use intensity (LUI) are estimated to be negatively correlated with ecosystem health. (3) Annual average precipitation (AMP) significantly improves ecosystem health, whereas annual average temperature (AMT) significantly worsens eco-health in the eastern and northern regions. LUI negatively impacts ecosystem health in western counties (such as Alxa, Ordos, and Baynnur). This study contributes to extending our understanding of ecosystem health depending on spatial scale and can inform decision-makers about how to control various influencing factors to improve the local ecology under local conditions. Finally, this study also proposes some relevant policy suggestions and provides effective ecosystem preservation and management support in Inner Mongolia.

First report of Fusarium foetens causing root rot on lavender (Lavandula angustifolia) in China - Xue-Jun Wei; Bing-Guo Jia; Xing Wang; Nan-Yang Li; Su-Na Wang; Li Li; Ai Zhang; Hao-Tian Zhang; Li-Ping Wang (Journal of Plant Pathology, 2023)

Impact of aqueous environments on hydrogen peroxide activation by manganese oxides: Kinetics and the critical role of bicarbonate - Na Guo; Ruochun Zhang; Jingchen Li; Zhihan Sun; Teng Fei; Peizhe Sun (Chemosphere, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

KNOX transcription factor VvHB63 affects grape seed development by interacting with protein VvHB06 - Jin Yao; Songlin Zhang; Na Wu; Xingmei Li; Bilal Ahmad; Jiuyun Wu; Rongrong Guo; Xiping Wang (Plant Science, 2023)

Phytic acid is a new substitutable plant-derived antifungal agent for the seedling blight of Pinus sylvestris var. mongolica caused by Fusarium oxysporum - Na Li; Yu-Xuan Wu; Yun-Di Zhang; Shu-Ren Wang; Guo-Cai Zhang; Jing Yang (Pesticide Biochemistry and Physiology, 2023)

Multiple roles of ferric chloride in preparing efficient magnetic hydrochar for sorption of methylene blue from water solutions - Xiao-Na Sun; Kun Yu; Jiong-Hua He; Yan Chen; Jian-Zhong Guo; Bing Li (Bioresource Technology, 2023)

Obstructive sleep apnea-increased DEC1 regulates systemic inflammation and oxidative stress that promotes development of pulmonary arterial hypertension - Xiaoming Li; Xiang Zhang; Xiaozhi Hou; Xin Bing; Fangyuan Zhu; Xinhao Wu; Na Guo; Hui Zhao; Fenglei Xu; Ming Xia (Apoptosis, 2023)

Higher toxicity induced by co-exposure of polystyrene microplastics and chloramphenicol to Microcystis aeruginosa: Experimental study and molecular dynamics simulation - Na Li; Zhuotong Zeng; Yafei Zhang; Hui Zhang; Ning Tang; Yihui Guo; Lan Lu; Xin Li; Ziqian Zhu; Xiang Gao; Jie Liang (Science of The Total Environment, 2023)

Cobalt nanoparticles induce mitochondrial damage and β-amyloid toxicity via the generation of reactive oxygen species - Jingrong Chen; Cheng Chen; Na Wang; Chunyu Wang; Zhaohui Gong; Jingxian Du; Honglin Lai; Xinpei Lin; Wei Wang; Xiangyu Chang; Michael Aschner; Zhenkun Guo; et al. (NeuroToxicology, 2023)

Construction of hemp seed protein isolate-phosphatidylcholine stablized oleogel-in-water gel system and its effect on structural properties and oxidation stability - Tong Wang; Na Li; Wang Zhang; Yanfei Guo; Dianyu Yu; Jinju Cheng; Liqi Wang (Food Chemistry, 2023)

The combined effects of NaCl-pH and urea-pH on the phase separation of type-A gelatin and dextran - Qi Wang; Bo Cui; Li Guo; Zhao Li; Qingqing Chai; Na Wang; Die Dong; Katsuyoshi Nishinari; Meng Zhao (Food Hydrocolloids, 2023)

Enhanced H2O2 formation and norfloxacin removal by electro-Fenton process using a surface-reconstructed graphite felt cathode: New insight into synergistic mechanism of defective active sites - Hongkai Guo; Chengwen Zhao; Hu Xu; Honglin Hao; Ziyuan Yang; Na Li; Weijun Xu (Environmental Research, 2023)

Granulation of Mn-based perovskite adsorbent for cyclic Hg0 capture from coal combustion flue gas - Jianping Yang; Yuanyuan Na; Yingchao Hu; Penglin Zhu; Fanyue Meng; Qingjie Guo; Zequn Yang; Wenqi Qu; Hailong Li (Chemical Engineering Journal, 2023)

Effect of grazing exclusion on emission of greenhouse gases and soil organic carbon turnover in alpine shrub meadow - Zhiqiang Dang; Na Guo; Shanshan Li; A. Allan Degen; Jingjuan Cao; Bin Deng; Aidong Wang; Zhen Peng; Luming Ding; Ruijun Long; Zhanhuan Shang (Science of The Total Environment, 2023)

Modulations in protein phosphorylation explain the physiological responses of barley (Hordeum vulgare) to nanoplastics and ZnO nanoparticles - Junhong Guo; Shuxin Li; Marian Brestic; Na Li; Peng Zhang; Lei Liu; Xiangnan Li (Journal of Hazardous Materials, 2023)

Effects of fine ambient particulate matters on de novo hypertensive disorders of pregnancy and blood pressure before 20 weeks - Zhichao Yuan; Qin Li; Tao Su; Jie Yang; Junjun Chen; Yuanzhou Peng; Shuang Zhou; Heling Bao; Shusheng Luo; Hui Wang; Jue Liu; Na Han; et al. (Environmental Research, 2023)

Biochar application reduces residual napropamide in the rhizosphere and improves soil microbial diversity - Ni Ni; Renyong Shi; Qiang Gao; Xiaona Li; Xinyan Guo; Xiaohui Zhang; Mali Shi; Yang Song; Yang Li; Na Wang; Xiaofei Zhang (Biology and Fertility of Soils, 2023)

Modeling Secondary Organic Aerosols in China: State of the Art and Perspectives - Jingyi Li; Haowen Zhang; Lin Li; Fei Ye; Hongli Wang; Song Guo; Na Zhang; Momei Qin; Jianlin Hu (Current Pollution Reports, 2023)

The aggregation of natural inorganic colloids in aqueous environment: A review - Yihui Guo; Ning Tang; Jiayin Guo; Lan Lu; Na Li; Tingting Hu; Ziqian Zhu; Xiang Gao; Xiaodong Li; Longbo Jiang; Jie Liang (Chemosphere, 2023)

Collagen-anchored cascade nanoreactors with prolonged intratumoral retention for combined cancer starvation and chemotherapy - Jingqing Mu; Yuyuan Du; Xingwei Li; Ran Yan; Haiping Zhong; Maoyu Cai; Na Yu; Jinchao Zhang; Xiaoyong Yuan; Xia Hua; Shutao Guo (Chemical Engineering Journal, 2023)

Self-healing properties of retrograded starch films with enzyme-treated waxy maize starch as healing agent - Li Guo; Na Yang; Wei Gao; Haiteng Tao; Bo Cui; Pengfei Liu; Feixue Zou; Lu Lu; Yishan Fang; Zhengzong Wu (Carbohydrate Polymers, 2023)

Roles of microRNAs and exosomes in Helicobacter pylori associated gastric cancer - Xiao-Han Xu; Shu-Li Shao; Dong Guo; Li-Na Ge; Zan Wang; Peng Liu; Yuan-Yong Tao (Molecular Biology Reports, 2023)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

The small RNA STnc1480 contributes to the regulation of biofilm formation and pathogenicity in Salmonella typhimurium - Jing Li; Chengcheng Ning; Na Li; Yun Guo; Chunhui Ji; Xiaozhen Zhu; Xingxing Zhang; Qingling Meng; Xianzhu Xia; Xuepeng Cai; Jun Qiao (Archives of Microbiology, 2022)

Higher pH is associated with enhanced co‐occurrence network complexity, stability and nutrient cycling functions in the rice rhizosphere microbiome - Yaping Guo; Bin Song; Anqi Li; Qi Wu; Haili Huang; Na Li; Ying Yang; Jonathan Miles Adams; Lin Yang (Environmental Microbiology, 2022)
The rice rhizosphere microbiota is crucial for crop yields and nutrient use efficiency. However, little is known about how co‐occurrence patterns, keystone taxa and functional gene assemblages relate to soil pH in the rice rhizosphere soils. Using shotgun metagenome analysis, the rice rhizosphere microbiome was investigated across 28 rice fields in east‐central China. At higher pH sites, the taxonomic co‐occurrence network of rhizosphere soils was more complex and compact, as defined by higher average degree, graph density and complexity. Network stability was greatest at medium pH (6.5

Green surfactant-modified TiO2 nanoparticles doped with La-Cr bimetal for NOx removal - Wen Nie; Weiwei Zhou; Na Li; Yun Hua; Qiu Bao; Jiayi Yan; Mingyue Yuan; Cheng Guo; Fengning Yu; Wenjin Niu; Chengyi Liu (Environmental Science and Pollution Research, 2022)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

Transposon insertions within alleles of BnaFT.A2 are associated with seasonal crop type in rapeseed - Qingdong Jin; Gengdong Gao; Chaocheng Guo; Taihua Yang; Ge Li; Jurong Song; Na Zheng; Shuai Yin; Licong Yi; Zhen Li; Xianhong Ge; Graham J. King; et al. (Theoretical and Applied Genetics, 2022)

Maternal exposure to cooking oil fumes during pregnancy and autistic‐like behaviors in Chinese preschoolers - Jian-Hui Yang; Esben Strodl; Chuan-An Wu; Xiang-Yu Hou; Xiao-Na Yin; Guo-Min Wen; Deng-Li Sun; Dan-Xia Xian; Jing-Yi Chen; Ying-Jie Chen; Jing Chen; Wei-Qing Chen (Environmental Science and Pollution Research, 2022)

BDS-3 and GPS/Galileo integrated PPP using broadcast ephemerides - Guo Chen; Na Wei; Min Li; Qile Zhao; Jiangnan Zhang (GPS Solutions, 2022)

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

Transcriptome Analysis of Greenfin Horse-Faced Filefish (Thamnaconus septentrionalis) Gills in Response to Amyloodinium ocellatum (AO) Infection - Li-Guo Yang; Yue Wang; Wen-Bin Xu; Bo Qin; Na Ying; Xue-Feng Song; Yan-Feng Yue; Xiao-Shan Wang; Bian-Bian Zhang; Yan-Qing Wu (Fishes, 2022)
The greenfin horse-faced filefish (Thamnaconus septentrionalis) is susceptible to recurrent Amyloodinium ocellatum (AO) infestation over the grow-out production cycle. This parasite breeds mainly on the gills, causing hypoxia in the fish body, and leading to many deaths. The host-parasite response drives a complex immune reaction, which is poorly understood. To generate a model for host-parasite interaction and the pathogenesis of AO in greenfin horse-faced filefish, an RNA-seq approach, differential gene expression, GO, and KEGG analyses were employed. Overall, 624 new genes and 2076 differentially expressed genes (DEGs) were detected, including 942 upregulated and 1134 downregulated genes in the gills. Compared with the control group, the expression of leptin a, GTPase IMAP family member 4, and NLR family CARD domain-containing protein 3 was significantly higher in the AO-infected group. Conversely, cell wall integrity and stress response component 1-like, and hepcidin-like were significantly downregulated in the gills of AO-infected fish. GO and KEGG enrichment analysis indicated that DEGs were significantly enriched in signaling pathways associated with viral protein interaction with cytokine and cytokine receptor and cytokine–cytokine receptor interaction. Collectively, this transcriptomic study provides novel molecular insights into the pathology caused by AO infestation and alternative theories for future research implementing strategies to control and manage AO.

Modeling-Based Multiscale Deep Prospectivity Mapping: A Case Study of the Haoyaoerhudong Gold Deposit, Inner Mongolia, China - Nan Li; Rui Cao; HuiShou Ye; Qiang Li; Yitian Wang; Xiping Lv; Na Guo; Yuanxiang Su; Jianrui Hao; Shitao Yin; Wenkai Chu (Natural Resources Research, 2022)

Non-peer-reviewed data, effect measures, and meta-regression analysis on proton pump inhibitor use and COVID-19 - Dan-Na Wu; Li-Rong Jiao; Guo-Fu Li; Guo Yu (European Journal of Clinical Pharmacology, 2022)

Why empresses have more sons? Maternal instant social condition determines it - Yan-Peng Li; Wei Ding; Zhi-Pang Huang; Ru-Liang Pan; Na Li; Guo-Peng Ren; Liang-Wei Cui; Qing-hua Cai; Wen Xiao (Behavioral Ecology and Sociobiology, 2022)
Sexual selection echoed by the sex ratio is a critical issue in evolution and reproductive biology studies, and the second sex ratio (sex ratio at birth, SRB) is an important evaluation indicator for sex regulation. However, broad debates on sex ratio at birth exist due to the lack of a clear spatiotemporal genealogical database. This study explicitly tests the Trivers and Willard’s hypothesis stating that parents with good social conditions tend to show a male-biased SRB. Using a database of Chinese imperial families from 211BC to 1912 (2142 years) which avoids the spatiotemporal confusion of data thanks to its clear boundaries and long timespan, we found that a proportion of males at birth was 0.54. In particular, the results indicate that the empresses generated a significantly higher male-biased SRB than the concubines within the imperial harems (0.61 vs 0.53), while the SRB of concubines was not higher than ordinary people (0.53 vs 0.52). A significant difference of SRB before and after empress coronation (0.48 vs 0.65) was detected, indicating that the change to a higher social status is the leading cause of a biased SRB. These findings suggest that mothers with privileged instant social conditions tend to generate more boys than girls. In other words, a higher maternal social rank during the conception period, instead of rich resources, forms the primary mechanism regulating the SRB. Significance statement Adaptive sex ratio has been a debatable topic difficult to clearly verify since the publication of Trivers and Willard Hypothesis in 1973, which proposes that parents who have good conditions should produce more male offspring. The one reason is that the validity and sample size of the databases used contained unavoidable confounding noise, both genealogically and genetically. To overcome these issues, we specifically compiled a historical database of Chinese imperial families, which are characterized by a confined mating harem and unique eunuch system, guaranteeing biological and genetic purity with precise genealogical relationships and genetic linkages between the parents and the offspring. Thus, this is an extraordinary effort to clarify the hypotheses proposed by TWH and other hypotheses.

Two LRR-Only Proteins Involved in Antibacterial Defense and Prophenoloxidase System of Swimming Crab Portunus trituberculatus - Ao Zhang; Yuan Liu; Na Guo; Shihao Li; Fuhua Li (Frontiers in Marine Science, 2022)
The leucine-rich repeat (LRR) motif is evolutionarily conserved in many pattern recognition receptors. Compared to the reported LRR proteins with multiple functional domains, the role of LRR-only proteins merely containing LRR motifs remain largely unexplored. In this study, two LRR-only proteins, PtLRR1 and PtLRR2, were identified from the swimming crab Portunus trituberculatus. Five LRR motifs with a consensus sequence LxxLxxLxLxxNxL were found in their encoded peptides. Both PtLRR1 and PtLRR2 were dominantly expressed in the hepatopancreas and showed a time-dependent response post bacteria and virus stimulation. The recombinant PtLRR1 could bind to various PAMPs, including LPS, PGN, and GLU. PtLRR1 and PtLRR2 displayed different regulatory activities in inducing the expression of inflammation and proPO system-related genes. Knockdown of PtLRR2 led to the decreased expression of the tested cytokines and adapter, while PtLRR1 knockdown enhanced the expression of serine proteases, serine protease homologues, and proPO genes. In addition, knockdown of PtLRR1 or PtLRR2 reduced the clearance activity of Vibrio but upregulated the expression levels of AMPs and key genes of Toll, IMD, and JNK pathways. These results suggest that PtLRR1 and PtLRR2 could act as potential immune receptors and regulate antibacterial immunity in crab.

Total, bioavailable and free 25-hydroxyvitamin D are associated with the prognosis of patients with non-small cell lung cancer - Si-Min Peng; Na Yu; Jun Che; Jia-Ying Xu; Guo-Chong Chen; Da-Peng Li; Yu-Song Zhang; Li-Qiang Qin (Cancer Causes & Control, 2022)

A superior allele of the wheat gene TaGL3.3-5B, selected in the breeding process, contributes to seed size and weight - Chaojie Wang; Lili Zhang; Yongdun Xie; Xiaofeng Guo; Yanfang Zhang; Yamin Zhang; Ahsan Irshad; Yuting Li; Huihui Qian; Doudou Jing; Guangyao Liu; Kaiming Wu; et al. (Theoretical and Applied Genetics, 2022)

Breast Cancer Awareness Based on Health Information Literacy and Influential Factors among Female Nursing Students in China - Shu Yang; Ping Li; Lin Yu; Na Liu; Jie Wang; Pingping Guo; Xuehui Zhang; Wei Zhang (Journal of Cancer Education, 2022)

Calycosin prevents IL-1β-induced articular chondrocyte damage in osteoarthritis through regulating the PI3K/AKT/FoxO1 pathway - Xiang Guo; Xiaoyu Pan; Jianhong Wu; Yuanzhou Li; Na Nie (In Vitro Cellular & Developmental Biology - Animal, 2022)

Potential Application of Biosurfactant-Producing Bacteria for Bioremediation of Oil Polluted Marine Intertidal Sediments - Ping Guo; Wei-Wei Xu; Dan-Na Wei; Man-Xia Zhang; Jin Zhang; Shi Tang; Bin-Xia Cao; Jian-Guo Lin; Wei Li (Journal of Marine Science and Engineering, 2022)
The removal of oil contaminants in marine intertidal sediments under cold climate is an urgent issue. Although the bioavailability of petroleum hydrocarbons decreases at low temperatures, biosurfactants can promote oil biodegradation. In this study, characteristics of biosurfactants produced by cold-adapted oil-degrading bacteria Planococcus sp. XW-1 were studied. Adding the XW-1 biosurfactant could effectively facilitate the solubility of phenanthrene, pyrene, diesel oil, and crude oil. The solubilization was limited by the number of rings and the molecular weight (WSRphenanthrene = 0.0234; WSRpyrene = 0.0165; WSRdiesel oil = 0.0027; WSRcrude oil = 0.0015). Additional biosurfactants significantly washed out crude oil adsorbed to the sand (reduction from 17.1%, 22.7% to 87.9% and 94.28% in 24 h). With the increase in particle size, the removal efficiency increased from 87.9% to 94.28%. After the addition of biosurfactant, the effect of degradation increased by 20% in 20 days. The results suggest that the biosurfactant-producing bacteria Planococcus sp. XW-1 is a promising candidate used in the in situ bioremediation of petroleum-contaminated intertidal sediment.

Heterogeneity of the Tissue-specific Mucosal Microbiome of Normal Grass Carp (Ctenopharyngodon idella) - Na Zhao; Jiamin Guo; Bo Zhang; Kai Liu; Yuting Liu; Yubang Shen; Jiale Li (Marine Biotechnology, 2022)

Quantifying discrepancies in the three-dimensional seasonal variations between IGS station positions and load models - Yujiao Niu; Na Wei; Min Li; Paul Rebischung; Chuang Shi; Guo Chen (Journal of Geodesy, 2022)

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Mass cultivation of conidia of Pyricularia oryzae - Zhong-na Hao; Hai-ping Qiu; Zhen Zhang; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2022)

Decreased incidence of acute hemorrhagic conjunctivitis associated with enhanced public health intervention during the COVID-19 epidemic in China, 2020 - Li Zhang; Xiangyu Guo; Hui Jiang; Na Zhao; Wei Cheng; Wangli Xu; Shelan Liu (Archives of Virology, 2022)

Comparative Study of Flood Coincidence Risk Estimation Methods in the Mainstream and its Tributaries - Na Li; Shenglian Guo; Feng Xiong; Jun Wang; Yuzuo Xie (Water Resources Management, 2022)

Promotional effect of ZrO2 and WO3 on bimetallic Pt-Pd diesel oxidation catalyst - Rongrong Fan; Zhaoqiang Li; Yu Wang; Yan Wang; Zhiyong Ding; Cheng Zhang; Na Kang; Xin Guo; Rong Wang (Environmental Science and Pollution Research, 2022)

Assessment of BDS-3 terrestrial reference frame realized by broadcast ephemeris: comparison with GPS/Galileo - Guo Chen; Na Wei; Min Li; Qile Zhao; Yujiao Niu; Hongliang Cai; Yinan Meng (GPS Solutions, 2022)

Differences in pathogenicity and physiologic races between Pyricularia oryzae isolates from indica and japonica rice varieties - Zhong-na Hao; Zhen Zhang; Hai-ping Qiu; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2021)

Atorvastatin Pretreatment Ameliorates Mesenchymal Stem Cell Migration through miR-146a/CXCR4 Signaling - Na Li; Xue-Yuan Guo; Jian Zhou; Xian-Liang Yan; Fang-Fang Yu (Tissue Engineering and Regenerative Medicine, 2021)

Establishment, characterization, and transfection potential of a new continuous fish cell line (CAM) derived from the muscle tissue of grass goldfish (Carassius auratus) - Na Li; Liwen Guo; Huarong Guo (In Vitro Cellular & Developmental Biology - Animal, 2021)

Associations of residential greenness with hypertension and blood pressure in a Chinese rural population: a cross-sectional study - Jie Jiang; Gongbo Chen; Baojing Li; Na Li; Feifei Liu; Yuanan Lu; Yuming Guo; Shanshan Li; Lifeng Chen; Hao Xiang (Environmental Science and Pollution Research, 2021)

Influences and mechanisms of nanoparticles on pentachloronitrobenzene accumulation by earthworms - Ming Li; Guanghui Xu; Na Guo; Na Zheng; Weihua Dong; Xiao Li; Yong Yu (Environmental Science and Pollution Research, 2021)

Effects of α-linolenic acid intake on blood lipid profiles：a systematic review and meta-analysis of randomized controlled trials - Hao Yue; Bin Qiu; Min Jia; Wei Liu; Xiao-fei Guo; Na Li; Zhi-xiang Xu; Fang-ling Du; Tongcheng Xu; Duo Li (Critical Reviews in Food Science and Nutrition, 2021)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

Gastrodin Regulates the Notch Signaling Pathway and Sirt3 in Activated Microglia in Cerebral Hypoxic-Ischemia Neonatal Rats and in Activated BV-2 Microglia - Jing Guo; Xiao-Li-Na Zhang; Zhang-Rui Bao; Xue-Ke Yang; Ling-Shuang Li; Yu Zi; Fan Li; Chun-Yun Wu; Juan-Juan Li; Yun Yuan (NeuroMolecular Medicine, 2021)

Exogenous Glutathione Alleviates Cadmium Toxicity in Wheat by Influencing the Absorption and Translocation of Cadmium - Ge-Zi Li; Shi-Juan Chen; Na-Ying Li; Ying-Ying Wang; Guo-Zhang Kang (Bulletin of Environmental Contamination and Toxicology, 2021)
Cadmium (Cd), a toxic heavy metal, is harmful to plants and human health. Glutathione (GSH) could alleviate Cd toxicity of plant species, whereas its mechanism responsible for wheat remains poorly understood. Here, we found that exogenous GSH application significantly increased the fresh and dry weight, root elongation, chlorophyll contents, while decreased the contents of malondialdehyde (MDA) and GSH, and translocation factor of Cd compared with Cd treatment. Moreover, GSH application significantly increased activities of antioxidant enzymes and expression of related genes, which involved in GSH synthesis, especially in roots. In addition, we found that GSH application suppressed Cd-induced expression of metal transporter genes TaNramp1 , TaNramp5 , TaHMA2 , TaHMA3 , TaLCT1 and TaIRT2 in roots. Taken together, our results suggested that GSH could alleviate Cd toxicity in wheat by increasing GSH synthesis gene expression or suppressing Cd transporter genes expression, and further affecting Cd uptake and translocation in wheat plants.

Genome-wide association analysis for yield-related traits at the R6 stage in a Chinese soybean mini core collection - Xiangnan Li; Yang Zhou; Yuanpeng Bu; Xinfang Wang; Yumei Zhang; Na Guo; Jinming Zhao; Han Xing (Genes & Genomics, 2021)

Effect of ambiguity resolution on the draconitic errors in sub-daily GPS position estimates - Shiwei Guo; Chuang Shi; Na Wei; Min Li; Lei Fan; Di Zhang (GPS Solutions, 2021)

Variations of soil organic matters and plant cuticular waxes along an altitude gradient in Qinghai-Tibet Plateau - Luhua Yao; Na Guo; Yuji He; Yu Xiao; Yang Li; Jianhua Gao; Yanjun Guo (Plant and Soil, 2021)

Culturally Tailored Intervention to Promote Mammography Screening Practice Among Chinese American Women: a Systematic Review - Xuehui Zhang; Ping Li; Pingping Guo; Jie Wang; Na Liu; Shu Yang; Lin Yu; Xiumin Zhang; Wei Zhang (Journal of Cancer Education, 2020)

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

Screening for natural inhibitors of human topoisomerases from medicinal plants with bio-affinity ultrafiltration and LC–MS - Minxia Fan; Guilin Chen; Baoqing Sun; Jianlin Wu; Na Li; Satyajit D. Sarker; Lutfun Nahar; Mingquan Guo (Phytochemistry Reviews, 2020)

Small RNA profiling reveal regulation of microRNAs in field peanut pod rot pathogen infection - Mian Wang; Chao-xin Zhang; Li-juan Pan; Tong Wang; Na Chen; Ming-na Chen; Zhen Yang; Xin-gang Guo; Shan-lin Yu; Xiao-yuan Chi (Biologia, 2020)

Removal algorithm of horizontal noise for echoes in mine geological radar - Yuxiu Guo; Na Liu; Xiaocun Huang; Jie Li (Arabian Journal of Geosciences, 2020)

Background‐dependent Wolbachia ‐mediated insecticide resistance in Laodelphax striatellus - Yongteng Li; Xiangdong Liu; Na Wang; Yueliang Zhang; Ary A. Hoffmann; Huifang Guo (Environmental Microbiology, 2020)
Summary Although facultative endosymbionts are now known to protect insect hosts against pathogens and parasitoids, the effects of endosymbionts on insecticide resistance are still unclear. Here we show that Wolbachia are associated with increased resistance to the commonly used insecticide, buprofezin, in the small brown planthopper ( Laodelphax striatellus ) in some genetic backgrounds while having no effect in other backgrounds. In three Wolbachia ‐infected lines from experimental buprofezin‐resistant strains and one line from a buprofezin‐susceptible line established from Chuxiong, Yunnan province, China, susceptibility to buprofezin increased after removal of Wolbachia . An increase in susceptibility was also evident in a Wolbachia ‐infected line established from a field population in Rugao, Jiangsu province. However, no increase was evident in two field populations from Nanjing and Fengxian, Jiangsu province, China. When Wolbachia was introgressed into different genetic backgrounds, followed by Wolbachia removal, the data pointed to Wolbachia effects that depend on the nuclear background as well as on the Wolbachia strain. However, there was no relationship between Wolbachia density and the component of buprofezin resistance associated with the symbiont. The results suggest that Wolbachia effects associated with chemical resistance are complex and unpredictable, but also that they can be substantial.

Production, Identification and Characterization of Erianthus rockii × Narenga porphyrocoma Intergeneric Hybrids as a New Germplasm for Sugarcane Breeding and Genetic Research - Hailong Chang; Qinnan Wang; Yongsheng Qiu; Yuanxia Qin; Xueting Li; Qingdan Wu; Weiping He; Yuqiang Guo; Wei Zhang; Junlv Chen; Na Fang (Sugar Tech, 2020)

Analysis of Myoglobin Stability and Bacterial Community Diversity in Mutton Chop Rolls During Cold Preservation - Xue-Qi Zhang; Tao Jiang; Na Guo; Li Bai; Dong-Mei Zhao (Current Microbiology, 2020)

Do fungal associates of co-occurring orchids promote seed germination of the widespread orchid species Gymnadenia conopsea? - Yue Gao; Zeyu Zhao; Jiayao Li; Na Liu; Hans Jacquemyn; Shunxing Guo; Xiaoke Xing (Mycorrhiza, 2020)

The sweet sorghum SbWRKY50 is negatively involved in salt response by regulating ion homeostasis - Yushuang Song; Jinlu Li; Yi Sui; Guoliang Han; Yi Zhang; Shangjing Guo; Na Sui (Plant Molecular Biology, 2020)

(±)-Quassidine K, a pair of cytotoxic bis- β -carboline alkaloid enantiomers from Picrasma quassioides - Xin-Ming Guo; Fei Li; Fang-Fang Zheng; Na-Na Gong; Yan Li; Wen-Zhou Feng; Lin Tian (Natural Product Research, 2020)

Characteristics and health risk assessment of heavy metals in street dust for children in Jinhua, China - Chad Joseph Bartholomew; Na Li; Yuanyuan Li; Weishuai Dai; Deborah Nibagwire; Ting Guo (Environmental Science and Pollution Research, 2020)

Physiological and biochemical responses of Dunaliella salina exposed to acrylamide - Na Ling; Hong-Xiu Li; Hong-Shi Guo; Xiu-Ming Cao; Xiao-Rui Liu (Biologia, 2019)

Vascularized composite allograft rejection is delayed by infusion of IFN-γ-conditioned BMSCs through upregulating PD-L1 - Yaojun Wang; Yunfeng Xi; Fu Han; Yang Liu; Na Li; Zhongliang Ren; Jiajie Xue; Lei Guo; Dahai Hu (Cell and Tissue Research, 2019)

Improving seed germination and oil contents by regulating the GDSL transcriptional level in Brassica napus - Li-Na Ding; Xiao-Juan Guo; Ming Li; Zheng-Li Fu; Su-Zhen Yan; Ke-Ming Zhu; Zheng Wang; Xiao-Li Tan (Plant Cell Reports, 2019)

Impact of surfactant and dissolved organic matter on uptake of atrazine in maize and its mobility in soil - Bing Bing Tian; Jing Hua Zhou; Fei Xie; Qian Nan Guo; Ai Ping Zhang; Xin Qiang Wang; Qian Qian Yu; Na Li; Hong Yang (Journal of Soils and Sediments, 2019)

BMAL1 regulates balance of osteogenic–osteoclastic function of bone marrow mesenchymal stem cells in type 2 diabetes mellitus through the NF-κB pathway - Xiaoguang Li; Na Liu; Bin Gu; Wei Hu; Ying Li; Bin Guo; Dongsheng Zhang (Molecular Biology Reports, 2018)

MiR-27b promotes sheep skeletal muscle satellite cell proliferation by targeting myostatin gene - Wei Zhang; Shi-Yin Wang; Shuang-Yi Deng; Li Gao; Li-Wei Yang; Xiao-Na Liu; Guo-Qing Shi (Journal of Genetics, 2018)

Antibiotic distribution, risk assessment, and microbial diversity in river water and sediment in Hong Kong - Wen-Jing Deng; Na Li; Guang-Guo Ying (Environmental Geochemistry and Health, 2018)

Overexpression of Chalcone Isomerase (CHI) Increases Resistance Against Phytophthora sojae in Soybean - Yang Zhou; Jian-li Huang; Xiao-li Zhang; Long-ming Zhu; Xin-fang Wang; Na Guo; Jin-ming Zhao; Han Xing (Journal of Plant Biology, 2018)

Genome-Wide Association Studies of Soybean Seed Hardness in the Chinese Mini Core Collection - Xing Zhang; Jinming Zhao; Yuanpeng Bu; Dong Xue; Zhangxiong Liu; Xiangnan Li; Jing Huang; Na Guo; Haitang Wang; Han Xing; Lijuan Qiu (Plant Molecular Biology Reporter, 2018)

Expression of BC1 Impairs Spatial Learning and Memory in Alzheimer’s Disease Via APP Translation - Tongmei Zhang; Pei Pang; Zemin Fang; Yu Guo; Hao Li; Xinyan Li; Tian Tian; Xin Yang; Wenting Chen; Shu Shu; Na Tang; Jianhua Wu; et al. (Molecular Neurobiology, 2018)

Conflicting meal recommendations for oral oncology drugs: pose risks to patient care? - Guo Yu; Dan-Na Wu; Yan Gong; Guo-Fu Li; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2018)

Stability analysis unit and spatial distribution pattern of the terrain texture in the northern Shaanxi Loess Plateau - Hu Ding; Jia-ming Na; Xiao-li Huang; Guo-an Tang; Kai Liu (Journal of Mountain Science, 2018)

Impact of IL-10-1082A/G gene polymorphism on the severity of EV71 infection in Chinese children - Qiubo Li; Hongfang He; Ya Guo; Yu Zhang; Peipei Liu; Yedan Liu; Chengqing Yang; Jie Song; Na Zhang; Zongbo Chen (Archives of Virology, 2018)

Special heterogeneous cytoplasm suppresses the expression of the gene producing multi-ovary in common wheat - Jialin Guo; Zheng Li; Gaisheng Zhang; Huali Tang; Qilu Song; Yulong Song; Shoucai Ma; Na Niu; Junwei Wang (Euphytica, 2017)

An investigation of the health effects caused by exposure to arsenic from drinking water and coal combustion: arsenic exposure and metabolism - Binggan Wei; Jiangping Yu; Chang Kong; Hairong Li; Linsheng Yang; Zhiwei Guo; Na Cui; Yajuan Xia; Kegong Wu (Environmental Science and Pollution Research, 2017)

Locus Mapping, Molecular Cloning, and Expression Analysis of rps6kb2, a Novel Metamorphosis-Related Gene in Chinese Tongue Sole (Cynoglossus semilaevis) - Yang Liu; Min Wei; Hua Guo; Changwei Shao; Liang Meng; Wenteng Xu; Na Wang; Lei Wang; Deborah M Power; Jilun Hou; Shahid Mahboob; Zhongkai Cui; et al. (Marine Biotechnology, 2017)

Transcriptional and Biochemical Alterations in Zebrafish Eleuthero-Embryos (Danio rerio) After Exposure to Synthetic Progestogen Dydrogesterone - Wen-Jun Shi; Guang-Guo Ying; Guo-Yong Huang; Yan-Qiu Liang; Li-Xin Hu; Jian-Liang Zhao; Jin-Na Zhang (Bulletin of Environmental Contamination and Toxicology, 2017)

The Adsorption Behavior of Pb2+ and Cd2+ in the Treated Black Soils with Different Freeze-Thaw Frequencies - Xu Wang; Yueming Li; Na Mao; Yanqiu Zhou; Ping Guo (Water, Air, & Soil Pollution, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

Post Plasma-Catalysis of Low Concentration VOC Over Alumina-Supported Silver Catalysts in a Surface/Packed-Bed Hybrid Discharge Reactor - Nan Jiang; Cheng Qiu; Lianjie Guo; Kefeng Shang; Na Lu; Jie Li; Yan Wu (Water, Air, & Soil Pollution, 2017)

miR-143 regulates proliferation and differentiation of bovine skeletal muscle satellite cells by targeting IGFBP5 - Wei Ran Zhang; Hui Na Zhang; Yi Min Wang; Yang Dai; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2017)

Identification and functional analysis of the GTPV bidirectional promoter region - Hui Zhang; Zhihua Sun; Na Zhang; Zhiqiang Li; Pengyan Wang; Qiang Fu; Yan Ren; Xuehua Shao; Yu Zhang; Zhiru Guo; Chuangfu Chen (Archives of Microbiology, 2017)

Arsenic methylation and skin lesions in migrant and native adult women with chronic exposure to arsenic from drinking groundwater - Binggan Wei; Jiangping Yu; Linsheng Yang; Hairong Li; Yuanqing Chai; Yajuan Xia; Kegong Wu; Jianwei Gao; Zhiwei Guo; Na Cui (Environmental Geochemistry and Health, 2017)

Successful treatment of accessory breast cancer with endocrine therapy - Chun-xi Wang; Shu-li Guo; Li-na Han (Journal of Zhejiang University-SCIENCE B, 2017)

Different responses of soybean cyst nematode resistance between two RIL populations derived from Peking × 7605 under two ecological sites - YONGCHUN LI; NA GUO; JINMING ZHAO; BIN ZHOU; RAN XU; HUI DING; WEIGUO ZHAO; JUNYI GAI; HAN XING (Journal of Genetics, 2016)

Melatonin attenuates angiotensin II-induced cardiomyocyte hypertrophy through the CyPA/CD147 signaling pathway - Hongyan Su; Jingyuan Li; Tongshuai Chen; Na Li; Jie Xiao; Shujian Wang; Xiaobin Guo; Yi Yang; Peili Bu (Molecular and Cellular Biochemistry, 2016)

Prognostic significance of FLT3-ITD in pediatric acute myeloid leukemia: a meta-analysis of cohort studies - Xiaoli Wu; Xuefeng Feng; Xiaoqing Zhao; Futian Ma; Na Liu; Hongming Guo; Chaonan Li; Huan Du; Baoxi Zhang (Molecular and Cellular Biochemistry, 2016)

Arctigenin Confers Neuroprotection Against Mechanical Trauma Injury in Human Neuroblastoma SH-SY5Y Cells by Regulating miRNA-16 and miRNA-199a Expression to Alleviate Inflammation - Jie Song; Na Li; Yang Xia; Zhong Gao; Sa-Feng Zou; Yu-Hui Yan; Shao-Heng Li; Yue Wang; Ya-Kun Meng; Jing-Xian Yang; Ting-Guo Kang (Journal of Molecular Neuroscience, 2016)

Loci and candidate gene identification for resistance to Phytophthora sojae via association analysis in soybean [Glycine max (L.) Merr.] - Lihong Li; Na Guo; Jingping Niu; Zili Wang; Xiaoxia Cui; Jutao Sun; Tuanjie Zhao; Han Xing (Molecular Genetics and Genomics, 2016)

Globular CTRP9 inhibits oxLDL-induced inflammatory response in RAW 264.7 macrophages via AMPK activation - Peng Zhang; Chengmin Huang; Jun Li; Tingting Li; Haipeng Guo; Tianjiao Liu; Na Li; Qing Zhu; Yuan Guo (Molecular and Cellular Biochemistry, 2016)

Study on effects of endophytes on growth and production of Z-Ligustilide and ferulic acid in Angelica sinensis - Xin-Guo Zhang; Xiao-Ru Li; Qiang-Lin Wang; Wen-Na Wang; Xiao-Qian Chen (Brazilian Journal of Botany, 2016)

Wogonoside induces growth inhibition and cell cycle arrest via promoting the expression and binding activity of GATA-1 in chronic myelogenous leukemia cells - Hui Li; Hui Hui; Jingyan Xu; Hao Yang; Xiaoxiao Zhang; Xiao Liu; Yuxin Zhou; Zhiyu Li; Qinglong Guo; Na Lu (Archives of Toxicology, 2016)

The influence of plant root system architectural properties upon the stability of loess hillslopes, Northeast Qinghai, China - Jiang-tao Fu; Xia-song Hu; Gary Brierley; Na Qiao; Qin-qin Yu; Hai-jing Lu; Guo-rong Li; Hai-li Zhu (Journal of Mountain Science, 2016)

Effects of Saline Water Irrigation and N Application Rate on NH3 Volatilization and N use Efficiency in a Drip-Irrigated Cotton Field - Guangwei Zhou; Wen Zhang; Lijuan Ma; Huijuan Guo; Wei Min; Qi Li; Na Liao; Zhenan Hou (Water, Air, & Soil Pollution, 2016)

Genome-wide identification and comparative analysis of grafting-responsive mRNA in watermelon grafted onto bottle gourd and squash rootstocks by high-throughput sequencing - Na Liu; Jinghua Yang; Xinxing Fu; Li Zhang; Kai Tang; Kateta Malangisha Guy; Zhongyuan Hu; Shaogui Guo; Yong Xu; Mingfang Zhang (Molecular Genetics and Genomics, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Arsenic Metabolites and Methylation Capacity Among Individuals Living in a Rural Area with Endemic Arseniasis in Inner Mongolia, China - Binggan Wei; Jiangping Yu; Hairong Li; Linsheng Yang; Yajuan Xia; Kegong Wu; Jianwei Gao; Zhiwei Guo; Na Cui (Biological Trace Element Research, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Inhibitory effect of totarol on exotoxin proteins hemolysin and enterotoxins secreted by Staphylococcus aureus - Ce Shi; Xingchen Zhao; Wenli Li; Rizeng Meng; Zonghui Liu; Mingyuan Liu; Na Guo; Lu Yu (World Journal of Microbiology and Biotechnology, 2015)

ATF6 pathway of unfolded protein response mediates advanced oxidation protein product-induced hypertrophy and epithelial-to-mesenchymal transition in HK-2 cells - Xun Tang; Xiujie Liang; Minhui Li; Tingting Guo; Na Duan; Yue Wang; Guang Rong; Lei Yang; Shaojie Zhang; Jun Zhang (Molecular and Cellular Biochemistry, 2015)

Separation of inhomogeneous blended seismic data - Qiang Liu; Li-Guo Han; Jing-Yi Chen; Xue Chen; Xian-Na Zhang (Applied Geophysics, 2015)

LYG-202 exerts antitumor effect on PI3K/Akt signaling pathway in human breast cancer cells - Yue Zhao; Xiaoping Wang; Yang Sun; Yuxin Zhou; Yuehan Yin; Youxiang Ding; Zhiyu Li; Qinglong Guo; Na Lu (Apoptosis, 2015)

Duration-dependent regulation of autophagy by isoflurane exposure in aged rats - Zheng-Qian Li; Lun-Xu Li; Na Mo; Yi-Yun Cao; Bolati Kuerban; Yao-Xian Liang; Dong-Sheng Fan; De-Hua Chui; Xiang-Yang Guo (Neuroscience Bulletin, 2015)

Within-litter variation in birth weight: impact of nutritional status in the sow - Tao-lin Yuan; Yu-hua Zhu; Meng Shi; Tian-tian Li; Na Li; Guo-yao Wu; Fuller W. Bazer; Jian-jun Zang; Feng-lai Wang; Jun-jun Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Morphological changes in gray matter volume correlate with catechol-O-methyl transferase gene Val158Met polymorphism in first-episode treatment-naïve patients with schizophrenia - Ming-Li Li; Bo Xiang; Yin-Fei Li; Xun Hu; Qiang Wang; Wan-Jun Guo; Wei Lei; Chao-Hua Huang; Lian-Sheng Zhao; Na Li; Hong-Yan Ren; Hui-Yao Wang; et al. (Neuroscience Bulletin, 2015)

Signals induced by exogenous nitric oxide and their role in controlling brown rot disease caused by Monilinia fructicola in postharvest peach fruit - Jing Ying Shi; Na Liu; Rong Xin Gu; Li Qin Zhu; Chang Zhang; Qing Guo Wang; Zhong Hua Lei; Yun Yun Liu; Ji Yun Ren (Journal of General Plant Pathology, 2015)

Effects of different cleaning treatments on heavy metal removal of Panax notoginseng (Burk) F. H. Chen - Liu Dahui; Xu Na; Wang Li; Cui Xiuming; Guo Lanping; Zhang Zhihui; Wang Jiajin; Yang Ye (Food Additives & Contaminants: Part A, 2014)

Isocitrate lyase is required for urediniospore germination of Puccinia striiformis f. sp. tritici - Jie Liu; Qiu-Ling Wang; Qing Chang; Li-Na Han; Guo-Liang Pei; Yue-Qing Xue; Lu-Meng Jia; Kun Zhang; Yuan-Yuan Duan; Zhen-Sheng Kang (Molecular Biology Reports, 2014)

Expression and Selection of Human Foxm1c Binding Peptides and Their Inhibitions on MCF7 Cancer Cells - Jian Cui; Jiaming Huang; Tailin Guo; Fang Wu; Zhijuan Liang; Lili Xiong; Tingting Huang; Li Zeng; Na Liu; Canquan Mao (International Journal of Peptide Research and Therapeutics, 2014)

Erratum to: Overexpression of Human E46K Mutant α-Synuclein Impairs Macroautophagy via Inactivation of JNK1-Bcl-2 Pathway - Jia-Qing Yan; Yu-He Yuan; Yan-Na Gao; Ju-Yang Huang; Kai-Li Ma; Yan Gao; Wan-Qing Zhang; Xiao-Feng Guo; Nai-Hong Chen (Molecular Neurobiology, 2014)

Overexpression of Human E46K Mutant α-Synuclein Impairs Macroautophagy via Inactivation of JNK1-Bcl-2 Pathway - Jia-Qing Yan; Yu-He Yuan; Yan-Na Gao; Ju-Yang Huang; Kai-Li Ma; Yan Gao; Wan-Qing Zhang; Xiao-Feng Guo; Nai-Hong Chen (Molecular Neurobiology, 2014)

Influence of ciprofloxacin on microbial community structure and function in soils - Hao Cui; Shu-Ping Wang; Jin Fu; Zhi-Qiang Zhou; Na Zhang; Li Guo (Biology and Fertility of Soils, 2014)

Association mapping for partial resistance to Phytophthora sojae in soybean (Glycine max (L.) Merr.) - JUTAO SUN; NA GUO; JUN LEI; LIHONG LI; GUANJUN HU; HAN XING (Journal of Genetics, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Haemocyte Apoptosis of the Tiger Shrimp Penaeus monodon Exposed to Cadmium - Jian-An Xian; Bin Li; Hui Guo; Yu-Tao Miao; Jian-Min Ye; Li-Na Feng; Chao-Xia Ye; Xun-Bin Pan; An-Li Wang; Xuan-Ming Hao (Bulletin of Environmental Contamination and Toxicology, 2014)

Genetic analysis and fine mapping of RpsJS, a novel resistance gene to Phytophthora sojae in soybean [Glycine max (L.) Merr.] - Jutao Sun; Lihong Li; Jinming Zhao; Jing Huang; Qiang Yan; Han Xing; Na Guo (Theoretical and Applied Genetics, 2014)

Comparative expression analysis of five WRKY genes from Tibetan hulless barley under various abiotic stresses between drought-resistant and sensitive genotype - Huie Li; Qiqiang Guo; Xiaozhong Lan; Qi Zhou; Na Wei (Acta Physiologiae Plantarum, 2014)

Three Novel SNPs in the Coding Region of the Bovine MC3R Gene and Their Associations with Growth Traits - Zhuo Ma Luoreng; Xing Ping Wang; Yun Ma; Feng Li; Dong Sheng Guo; Na Li; Jin Ren Wang (Biochemical Genetics, 2014)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)

An exploratory analysis of benthic macroinvertebrates as indicators of the ecological status of the Upper Yellow and Yangtze Rivers - Baozhu Pan; Zhaoyin Wang; Zhiwei Li; Guo-an Yu; Mengzhen Xu; Na Zhao; Gary Brierley (Journal of Geographical Sciences, 2013)

CD73+ adipose-derived mesenchymal stem cells possess higher potential to differentiate into cardiomyocytes in vitro - Qiong Li; Li-Jie Qi; Zhi-Kun Guo; He Li; Hong-Bo Zuo; Na-Na Li (Journal of Molecular Histology, 2013)

An exploratory analysis of vegetation strategies to reduce shallow landslide activity on loess hillslopes, Northeast Qinghai-Tibet Plateau, China - Xia-song Hu; Gary Brierley; Hai-li Zhu; Guo-rong Li; Jiang-tao Fu; Xiao-qing Mao; Qin-qin Yu; Na Qiao (Journal of Mountain Science, 2013)
Heavy summer rainfall induces significant soil erosion and shallow landslide activity on the loess hillslopes of the Xining Basin at the northeast margin of the Qinghai-Tibet Plateau. This study examines the mechanical effects of five native shrubs that can be used to reduce shallow landslide activity. We measured single root tensile resistance and shear resistance, root anatomical structure and direct shear and triaxial shear for soil without roots and five rootsoil composite systems. Results show that Atriplex canescens (Pursh) Nutt. possessed the strongest roots, followed by Caragana korshinskii Kom., Zygophyllum xanthoxylon (Bunge) Maxim., Nitraria tangutorum Bobr. and Lycium chinense Mill. Single root strength and shear resistance relationships with root diameter are characterized by power or exponential relations, consistent with the Mohr-Coulomb law. Root mechanical strength reflects their anatomical structure, especially the percentage of phloem and xylem cells, and the degree and speed of periderm lignifications. The cohesion force of root-soil composite systems is notably higher than that of soil without roots, with increasing amplitudes of cohesion force for A. canescens , C. korshinskii , Z. xanthoxylon , N. tangutorum and L. chinense of 75.9%, 75.1%, 36.2%, 24.6% and 17.0 % respectively. When subjected to shear forces, the soil without root samples show much greater lateral deformation than the root-soil composite systems, reflecting the restraining effects of roots. Findings from this paper indicate that efforts to reduce shallow landslides in this region by enhancing root reinforcement will be achieved most effectively using A. canescens and C. korshinskii .

Alterations of liver histology and blood biochemistry in blunt snout bream Megalobrama amblycephala fed high-fat diets - Kang-le Lu; Wei-na Xu; Jun-yi Li; Xiang-fei Li; Guo-qing Huang; Wen-bin Liu (Fisheries Science, 2013)

Surgical Trauma Induces Iron Accumulation and Oxidative Stress in a Rodent Model of Postoperative Cognitive Dysfunction - Li-Na An; Yang Yue; Wen-Zhi Guo; Yu-Liang Miao; Wei-Dong Mi; Hong Zhang; Zhi-Li Lei; Shu-Jun Han; Lan Dong (Biological Trace Element Research, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Benfotiamine prevents increased β-amyloid production in HEK cells induced by high glucose - Xiao-Jing Sun; Lei Zhao; Na Zhao; Xiao-Li Pan; Guo-Qiang Fei; Li-Rong Jin; Chun-Jiu Zhong (Neuroscience Bulletin, 2012)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

Molecular cloning, characterization expression of P450c17-I and P450c17-II and their functions analysis during the reproductive cycle in males of barfin flounder (Verasper moseri) - Guo X. Jin; Hai S. Wen; Feng He; Ji F. Li; Cai F. Chen; Jia R. Zhang; Xiao Y. Chen; Bao Shi; Dan Shi; Yan P. Yang; Bao X. Qi; Na Li (Fish Physiology and Biochemistry, 2012)

Genome-Wide Expression Profiling of the Response to Linezolid in Mycobacterium tuberculosis - Junchao Liang; Xudong Tang; Na Guo; Kaiyu Zhang; Aizhen Guo; Xiuping Wu; Xuelin Wang; Zhenhong Guan; Lihui Liu; Fengge Shen; Mingxun Xing; Liqiang Liu; et al. (Current Microbiology, 2012)

−251 T/A polymorphism of the interleukin-8 gene and cancer risk: a HuGE review and meta-analysis based on 42 case–control studies - Na Wang; Rongmiao Zhou; Chunmei Wang; Xiaoqing Guo; Zhifeng Chen; Shan Yang; Yan Li (Molecular Biology Reports, 2012)

Down-regulation of β3-integrin inhibits bone metastasis of small cell lung cancer - Na Li; Jian-ping Zhang; Shan Guo; Jie Min; Li–li Liu; Hai-chuan Su; Ying-ming Feng; He-long Zhang (Molecular Biology Reports, 2012)

Quantitative analysis of expression of six BmGST genes in silkworm, Bombyx mori - Guo-dong Zhao; Yi-ling Zhang; Rui-na Gao; Rui-xian Wang; Ting Zhang; Bing Li; Yi Zhang; Chang-de Lu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2011)

Global transcriptional profiles of Mycobacterium tuberculosis treated with plumbagin - Haiqing Ye; Zengshan Liu; Aizhen Guo; Junchao Liang; Na Guo; Fanli Zeng; Liqiang Liu; Lei Li; Jing Jin; Xiuping Wu; Yang Li; Mingyuan Liu; et al. (World Journal of Microbiology and Biotechnology, 2011)

Influence of temperature and medium on viability of Demodex folliculorum and Demodex brevis (Acari: Demodicidae) - Ya-E Zhao; Na Guo; Li-Ping Wu (Experimental and Applied Acarology, 2011)

Effects of MboII and BspMI polymorphisms in the gonadotropin releasing hormone receptor (GnRHR) gene on sperm quality in Holstein bulls - Wu-Cai Yang; Ke-Qiong Tang; Jun-Na Yu; Chun-Yan Zhang; Xiao-Xia Zhang; Li-Guo Yang (Molecular Biology Reports, 2011)

Expression of a novel thermostable Cu, Zn-superoxide dismutase from Chaetomium thermophilum in Pichia pastoris and its antioxidant properties - Li-Qing Zhang; Fang-Xian Guo; Hong-Quan Xian; Xiu-Juan Wang; An-Na Li; Duo-Chuan Li (Biotechnology Letters, 2011)

Supplemental Selenium Alleviates the Toxic Effects of Excessive Iodine on Thyroid - Jian Xu; Xiao-Li Liu; Xue-Feng Yang; Huai-Lan Guo; Li-na Zhao; Xiu-Fa Sun (Biological Trace Element Research, 2011)

Microarray Analysis of the Chelerythrine-Induced Transcriptome of Mycobacterium tuberculosis - Junchao Liang; Fanli Zeng; Aizhen Guo; Liqiang Liu; Na Guo; Lei Li; Jing Jin; Xiuping Wu; Mingyuan Liu; Dan Zhao; Yang Li; Qi Jin; et al. (Current Microbiology, 2011)

Genetic typing and epidemiologic observation of bovine viral diarrhea virus in Western China - Fagang Zhong; Na Li; Xin Huang; Yan Guo; Hongxiu Chen; Xinhua Wang; Changqing Shi; Xiaoying Zhang (Virus Genes, 2011)

An MspI polymorphism in the inhibin alpha gene and its associations with superovulation traits in Chinese Holstein cows - Ke-Qiong Tang; Shu-Jing Li; Wu-Cai Yang; Jun-Na Yu; Li Han; Xiang Li; Li-Guo Yang (Molecular Biology Reports, 2011)

Cloning and expression of P450c17-I (17α-hydroxylase/17,20-lyase) in brain and ovary during gonad development in Cynoglossus semilaevis - Cai F. Chen; Hai S. Wen; Zhao P. Wang; Feng He; Jia R. Zhang; Xiao Y. Chen; Guo X. Jin; Bao Shi; Dan Shi; Yan P. Yang; Ji F. Li; Bao X. Qi; et al. (Fish Physiology and Biochemistry, 2010)

Design, expression and characterization of recombinant hybrid peptide Attacin-Thanatin in Escherichia coli - Li Na Wang; Bing Yu; Guo Quan Han; Jun He; Dai Wen Chen (Molecular Biology Reports, 2010)

Genetic evolution of equine influenza viruses isolated in China - Ting Qi; Wei Guo; Wen-Qiang Huang; Hong-Mei Li; Li-Ping Zhao; Ling-Li Dai; Na He; Xiao-Fang Hao; Wen-Hua Xiang (Archives of Virology, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Molecular cloning, expression in Escherichia coli of Attacin A gene from Drosophila and detection of biological activity - Li-Na Wang; Bing Yu; Guo-Quan Han; Dai-Wen Chen (Molecular Biology Reports, 2010)

The design and preparation of a flexible bio-chip for use as a visual prosthesis, and evaluation of its biological features - Li-Feng Chen; Ning Hu; Na Liu; Bingbing Guo; Junping Yao; Lu Xia; Xiaolin Zheng; Wensheng Hou; Zheng Qin Yin (Cell and Tissue Research, 2010)

Extended expression of B-class MADS-box genes in the paleoherb Asarum caudigerum - Yin-He Zhao; Michael Möller; Jun-Bo Yang; Ting-Song Liu; Jin-Feng Zhao; Li-Na Dong; Jin-Peng Zhang; Cheng-Yun Li; Guo-Ying Wang; De-Zhu Li (Planta, 2010)

STR Polymorphisms of the Henan Population and Investigation of the Central Plains Han Origin of Chaoshanese - Li-Na Xu; Sheng-Ping Hu; Guo-Ying Feng (Biochemical Genetics, 2009)

An investigation on the polymorphisms of two DNA repair genes and susceptibility to ESCC and GCA of high-incidence region in northern China - Na Wang; Xiu-juan Dong; Rong-miao Zhou; Wei Guo; Xiao-juan Zhang; Yan Li (Molecular Biology Reports, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Death and proliferation of chondrocytes in the degraded mandibular condylar cartilage of rats induced by experimentally created disordered occlusion - Kai Jiao; Mei-Qing Wang; Li-Na Niu; Juan Dai; Shi-Bin Yu; Xiao-Dong Liu; Guo-Wei Wang (Apoptosis, 2009)

Purification of recombinant laccase from Trametes versicolor in Pichia methanolica and its use for the decolorization of anthraquinone dye - Mei Guo; Fuping Lu; Minyao Liu; Tuoping Li; Jun Pu; Na Wang; Peng Liang; Chenyun Zhang (Biotechnology Letters, 2008)

Total Internal Reflection Fluorescence Spectroscopy for Investigating the Adsorption of a Porphyrin at the Glass/Water Interface in the Presence of a Cationic Surfactant Below the Critical Micelle Concentration - Yao-Ji Tang; Ying Chen; Min-Na Yao; Zhe-Xiang Zou; Guo-Bin Han; Yao-Qun Li (Journal of Fluorescence, 2008)

Effects of Water-borne Copper on the Y-organ and Content of 20-hydroxyecdysone in Eriocheir sinensis - Zhi-biao Yang; Yun-long Zhao; Na Li; Jian Yang; Xiu-guo Hua (Archives of Environmental Contamination and Toxicology, 2008)

A new linearly-combined bi-exponential model for kinetic analysis of the isometric relaxation process of Bufo gastrocnemius under electric stimulation in vitro - Rui Guo; Sheng-bing Li; Li-na Zhao; Yun-sheng Zhao; Wei Lu; Pei Yuan; Ping Deng; Fei Liao (Journal of Zhejiang University-SCIENCE B, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Optimization of covalent immobilization of pectinase on sodium alginate support - Tuoping Li; Na Wang; Suhong Li; Qiancheng Zhao; Mei Guo; Cheyun Zhang (Biotechnology Letters, 2007)

Association of MTHFR C677T and SHMT1 C1420T with susceptibility to ESCC and GCA in a high incident region of Northern China - Yimin Wang; Wei Guo; Yutong He; Zhifeng Chen; Denggui Wen; Xiufeng Zhang; Na Wang; Yan Li; Hui Ge; Jianhui Zhang (Cancer Causes & Control, 2007)

Relationship Between Phytohormones and Male Sterility in Thermo-Photo-Sensitive Genic Male Sterile (TGMS) Wheat - Jian-Kui Zhang; Xue-Feng Zong; Guo-Dong Yu; Jia-Na Li; Wen Zhang (Euphytica, 2006)

Pharmacokinetics of three proton pump inhibitors in Chinese subjects in relation to the CYP2C19 genotype - Hai-Ling Qiao; Yu-Rong Hu; Xin Tian; Lin-Jing Jia; Na Gao; Li-Rong Zhang; Yu-Zhong Guo (European Journal of Clinical Pharmacology, 2006)